Barrier film and polarizer with barrier film

By applying a barrier film containing a silicon oxide layer and a stain-resistant layer on the polarized plate, the problem of discoloration of the polarized plate under heating and humidification conditions is solved, and higher reliability and stability are achieved.

JP2025065756APending Publication Date: 2025-04-22NITTO DENKO CORP

Patent Information

Application Number
JP2023175178
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing polarized plates are prone to discoloration under heating and humidification conditions, resulting in degradation in performance.

Method used

A barrier film consisting of a transparent matrix membrane, a hardened resin layer and an antifouling layer is used. The barrier film consists of a silicon oxide layer and an antifouling layer with a density of about 2.35 g/cm³.

Benefits of technology

Effectively suppress the discoloration of the polarized plate under heating and humidification conditions, and improve the reliability and stability of the polarized plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065756000001_ABST
    Figure 2025065756000001_ABST
Patent Text Reader

Abstract

To provide a barrier film which can suppress color change of a polarizer under a heating and humidifying condition, and a polarizer with the barrier film.SOLUTION: A barrier film 1 includes: a transparent base material film 2; and a barrier layer 4 arranged on one side of the transparent base material film 2 in a thickness direction. The transparent base material film 2 has a transparent resin film 21. The barrier layer 4 has at least one silicon oxide layer 42 and an anti-fouling layer 43 arranged on one side of the silicon oxide layer 42 in a thickness direction. The density of a silicon oxide layer 42, which is the closest to the anti-fouling layer 43 in the thickness direction, is at least 2.35 g / cm3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a barrier film and a barrier film-attached polarizing plate. [Background technology]

[0002] In image display devices such as liquid crystal displays and organic EL displays, a polarizing plate is arranged on at least one side of a display cell due to the image formation method. Such a polarizing plate is manufactured as follows. For example, a polarizer is formed on a resin substrate by applying a polyvinyl alcohol (PVA) resin to the resin substrate, and then the resin substrate is stretched and dyed. Then, a protective film is attached to the obtained polarizer, and the resin substrate is removed. A polarizing plate manufactured by such a method has a thin polarizer, and the use of this polarizing plate allows the image display device to be made thinner.

[0003] Furthermore, a polarizing plate with an antireflection layer has been proposed in which an antireflection film is attached to such a polarizing plate for the purpose of protecting the polarizing plate (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 163461 Brochure Summary of the Invention [Problem to be solved by the invention]

[0005] On the other hand, the polarizing plate is required to have high reliability under heated and humid conditions.

[0006] However, the polarizing plate with an antireflection layer described in Patent Document 1 has a problem in that the polarizing plate discolors under heated and humidified conditions.

[0007] The present invention provides a barrier film and a polarizing plate with a barrier film, which are capable of suppressing discoloration of the polarizing plate under heated and humidified conditions. [Means for solving the problem]

[0008] The present invention [1] is a method for manufacturing a laminated laminated laminated laminate comprising: a transparent substrate film having a transparent resin film; and a barrier layer disposed on one side in a thickness direction of the transparent substrate film, the barrier layer having at least one silicon oxide layer and an antifouling layer disposed on one side in a thickness direction of the silicon oxide layer, the density of the silicon oxide layer closest to the antifouling layer in the thickness direction being 2.35 g / cm. 3 The barrier film is as above.

[0009] The present invention [2] includes the barrier film according to [1], wherein the transparent substrate film further includes a cured resin layer disposed on one surface in the thickness direction of the transparent resin film.

[0010] The present invention [3] includes the barrier film according to [1] or [2], wherein the barrier film further comprises a primer layer, the primer layer being a metal oxide layer, and the primer layer is disposed on one thickness-wise side of the transparent substrate film and on the other thickness-wise side of the barrier layer.

[0011] The present invention [4] includes the barrier film according to any one of [1] to [3], wherein the barrier layer comprises an alternating laminate consisting of at least one niobium oxide layer and at least one silicon oxide layer, and the antifouling layer is disposed on one surface in the thickness direction of the alternating laminate.

[0012] The present invention [5] includes the barrier film according to any one of [1] to [3], wherein the barrier layer comprises a silicon oxide layer and the antifouling layer disposed on one surface of the silicon oxide layer in the thickness direction.

[0013] The present invention [6] includes a barrier film-attached polarizing plate comprising the barrier film according to any one of [1] to [5] and a polarizing plate disposed on the other side in the thickness direction of the barrier film.

[0014] The present invention [7] includes the polarizing plate with a barrier film according to [6], wherein the polarizing plate comprises a protective film and a polarizer, and the polarizer is a coating film of a polyvinyl alcohol resin.

[0015] The present invention [8] is a method to measure the change in chromaticity of transmitted light Δb under heating and humidifying conditions at 60°C and 90% RH for 240 hours. * The polarizing plate with a barrier film according to [6] or [7], wherein the refractive index is 0.5 or less. Effect of the Invention

[0016] The barrier film of the present invention comprises a transparent substrate film comprising a transparent resin film and a cured resin layer disposed on one surface of the transparent resin film in the thickness direction, and a barrier layer disposed on one side of the transparent substrate film in the thickness direction. The barrier layer comprises at least one silicon oxide layer and an antifouling layer disposed on one side of the silicon oxide layer in the thickness direction. The density of the silicon oxide layer closest to the antifouling layer in the thickness direction is 2.35 g / cm. 3 Therefore, when the film is used in a polarizing plate, discoloration of the polarizing plate under heated and humidified conditions can be suppressed.

[0017] The barrier film-attached polarizing plate of the present invention includes the above-mentioned barrier film, and therefore discoloration of the polarizing plate under heated and humidified conditions can be suppressed. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 shows a cross-sectional view of a first embodiment of the barrier film of the present invention. [Diagram 2]Figure 2 shows a method for producing the barrier film shown in Figure 1. Figure 2A shows a step of preparing a transparent resin film, Figure 2B shows a step of forming a cured resin layer on the transparent resin film, Figure 2C shows a step of forming a primer layer on the cured resin layer, Figure 2D shows a step of forming an alternate laminate of a niobium oxide layer and a silicon oxide layer on the primer layer, and Figure 2E shows a step of forming an antifouling layer on the silicon oxide layer. [Diagram 3] FIG. 3 shows a cross-sectional view of a barrier film-attached polarizing plate using the barrier film shown in FIG. [Figure 4] Fig. 4 shows a method for producing the polarizing plate with a barrier film shown in Fig. 3. Fig. 4A shows a step of preparing a resin substrate, Fig. 4B shows a step of forming a coating film (polarizer) of a polyvinyl alcohol resin on the resin substrate, Fig. 4C shows a step of attaching a protective film onto the polarizer via an adhesive layer, Fig. 4D shows a step of removing the resin substrate, and Fig. 4E shows a step of attaching the barrier film shown in Fig. 1 onto the surface of the protective film. [Diagram 5] FIG. 5 shows a schematic diagram of a magnetron sputtering deposition apparatus used in the method for producing a barrier film. [Figure 6] FIG. 6 is an enlarged cross-sectional view of a magnetron plasma unit provided in the magnetron sputtering film formation apparatus shown in FIG. [Figure 7] FIG. 7 shows a cross-sectional view of the magnet unit of the first magnetron plasma unit. [Figure 8] FIG. 8 shows a cross-sectional view of the magnet unit of the second magnetron plasma unit. [Figure 9] FIG. 9 shows a cross-sectional view of a modified example of a polarizing plate with a barrier film. [Figure 10]Figure 10 shows a method for producing a barrier film in the polarizing plate with a barrier film shown in Figure 9. Figure 10A shows a step of preparing a transparent resin film, Figure 10B shows a step of forming a cured resin layer on the transparent resin film, Figure 10C shows a step of forming a primer layer on the cured resin layer, Figure 10D shows a step of forming a silicon oxide layer on the primer layer, and Figure 10E shows a step of forming an antifouling layer on the silicon oxide layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] 1. Barrier film One embodiment of the barrier film of the present invention will be described with reference to FIG.

[0020] The barrier film 1 is in the form of a film (including a sheet) having a predetermined thickness, as shown in Fig. 1. The barrier film 1 extends in a plane direction perpendicular to the thickness direction, and one surface (upper surface) and the other surface (lower surface) in the thickness direction of the barrier film 1 are flat.

[0021] The barrier film 1 includes a transparent substrate film 2 and a barrier layer 4 disposed on one side in the thickness direction of the transparent substrate film 2. The barrier film 1 may further include a primer layer 3 disposed on one side in the thickness direction of the transparent substrate film 2 and on the other side in the thickness direction of the barrier layer 4. Specifically, as shown in Fig. 1, the barrier film 1 includes a transparent substrate film 2, a primer layer 3 disposed on one surface in the thickness direction (upper surface) of the transparent substrate film 2, and a barrier layer 4 disposed on one surface in the thickness direction (upper surface) of the primer layer 3.

[0022] <Transparent substrate film> The transparent substrate film 2 is the bottom layer of the barrier film 1. The transparent substrate film 2 includes a transparent resin film 21. Furthermore, the transparent substrate film 2 further includes a cured resin layer 22 disposed on one surface of the transparent substrate film 2 in the thickness direction, as necessary. The transparent substrate film 2 preferably includes the transparent resin film 21 and the cured resin layer 22 disposed on one surface of the transparent resin film 21 in the thickness direction.

[0023] The transparent resin film 21 has a film shape (including a sheet shape) and is, for example, a transparent resin film having flexibility.

[0024] Examples of the material of the transparent resin film 21 include cellulose resin, polyester resin, (meth)acrylic resin (acrylic resin and / or methacrylic resin), olefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, polystyrene resin, norbornene resin, and polyvinyl alcohol resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of the cellulose resin include triacetyl cellulose (TAC). From the viewpoints of transparency, heat resistance, and mechanical strength, the transparent resin film 21 is preferably a cellulose-based film formed from a cellulose resin, and more preferably a triacetyl cellulose film. The materials of the transparent resin film 21 can be used alone or in combination of two or more kinds.

[0025] The transparent resin film 21 has a total light transmittance (JISK-7105) of, for example, 80% to 100%, preferably 85% to 100%, more preferably 88% to 100%, and still more preferably 90% to 100%.

[0026] The transparent resin film 21 has a total light transmittance (JISK-7105) of, for example, 80% or more, preferably 85% or more, more preferably 88% or more, still more preferably 90% or more, and for example, 100% or less.

[0027] The thickness of the transparent resin film 21 is not particularly limited, but from the viewpoints of strength and handleability, it is, for example, 5 μm to 300 μm, preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, even more preferably 30 μm to 170 μm, and particularly preferably 50 μm to 150 μm.

[0028] The thickness of the transparent resin film 21 is not particularly limited, but from the viewpoint of strength and handleability, it is, for example, 5 μm or more, preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, particularly preferably 50 μm or more, and for example, 300 μm or less, preferably 250 μm or less, more preferably 200 μm or less, even more preferably 170 μm or less, particularly preferably 150 μm or less.

[0029] The thickness of the transparent resin film 21 can be measured, for example, by using a thickness meter.

[0030] The cured resin layer 22 is a layer that improves the mechanical properties of the barrier film 1. The cured resin layer 22 is in contact with the surface of the transparent resin film 21 (one surface in the thickness direction), for example.

[0031] Examples of the cured resin layer 22 include a hard coat layer and an anti-blocking layer. The hard coat layer, for example, makes it difficult for scratches to form on the exposed surface of the transparent resin film 21. The anti-blocking layer imparts blocking resistance to the surfaces of the multiple barrier films 1 that are in contact with each other, for example, when the barrier films 1 are laminated in the thickness direction.

[0032] The cured resin layer 22 is, for example, a cured product of a curable resin composition. Specifically, the cured resin layer 22 can be formed by applying a curable resin composition to one surface in the thickness direction of the transparent resin film 21, drying the composition as necessary, and then curing the composition.

[0033] The curable resin composition contains a curable resin. Examples of the curable resin include polyester resin, acrylic urethane resin, acrylic resin (excluding acrylic urethane resin), urethane resin (excluding acrylic urethane resin), amide resin, silicone resin, epoxy resin, and melamine resin, and preferably includes acrylic resin (excluding acrylic urethane resin) and acrylic urethane resin. The curable resin can be used alone or in combination of two or more kinds.

[0034] In addition, examples of the curable resin composition include an ultraviolet-curable resin composition and a thermosetting resin composition. From the viewpoint of production efficiency, an ultraviolet-curable resin composition is preferably used as the curable resin composition. The ultraviolet-curable resin composition includes at least one selected from the group consisting of an ultraviolet-curable monomer, an ultraviolet-curable oligomer, and an ultraviolet-curable polymer. A specific example of the ultraviolet-curable resin composition includes a hard coat layer forming composition described in JP 2016-179686 A.

[0035] The curable resin composition preferably contains fine particles from the viewpoint of adjusting the hardness, adjusting the surface roughness, adjusting the refractive index, and imparting anti-glare properties to the cured resin layer 22. Examples of the fine particles include inorganic particles and organic particles, and preferably inorganic particles. Examples of the inorganic particles include inorganic oxide particles. Examples of the material of the inorganic oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide, and preferably silica. Examples of the material of the organic particles include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate.

[0036] The curable resin composition preferably contains a photopolymerization initiator. The curable resin composition may further contain additives such as a solvent, a leveling agent, a thixotropic agent, and an antistatic agent.

[0037] Examples of the solvent include butyl acetate, ethyl acetate, toluene, and cyclopentanone, and preferably, butyl acetate.

[0038] The thickness of the cured resin layer 22 is, for example, 0.1 μm to 15 μm, preferably 0.5 μm to 12 μm, and more preferably 1 μm to 10 μm.

[0039] The thickness of the cured resin layer 22 is, for example, 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more, and for example, 15 μm or less, preferably 12 μm or less, more preferably 10 μm or less.

[0040] When the thickness of the cured resin layer 22 is equal to or greater than the above lower limit, the cured resin layer 22 can be easily formed and the function of the cured resin layer 22 can be fully exerted. When the thickness of the cured resin layer is equal to or less than the above upper limit, the barrier film 1 can be made thinner.

[0041] One thickness-wise surface of the transparent substrate film 2 (one thickness-wise surface of the cured resin layer 22) may be subjected to a surface modification treatment such as corona treatment, plasma treatment, frame treatment, ozone treatment, primer treatment, glow treatment, saponification treatment, and treatment with a coupling agent, in order to improve adhesion to the primer layer 3 described later or the barrier layer 4 described later.

[0042] The transparent substrate film 2 has a total light transmittance (JISK-7105) of, for example, 80% to 100%, preferably 85% to 100%, more preferably 88% to 100%, and still more preferably 90% to 100%.

[0043] The transparent substrate film 2 has a total light transmittance (JISK-7105) of, for example, 80% or more, preferably 85% or more, more preferably 88% or more, still more preferably 90% or more, and for example, 100% or less.

[0044] The thickness of the transparent substrate film 2 is not particularly limited, but from the viewpoints of strength and handleability, it is, for example, 5 μm to 300 μm, preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, even more preferably 30 μm to 170 μm, and particularly preferably 50 μm to 150 μm.

[0045] The thickness of the transparent substrate film 2 is not particularly limited, but from the viewpoints of strength and handleability, it is, for example, 5 μm or more, preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, particularly preferably 50 μm or more, and for example, 300 μm or less, preferably 250 μm or less, more preferably 200 μm or less, even more preferably 170 μm or less, particularly preferably 150 μm or less.

[0046] <Primer layer> The primer layer 3 is an adhesive layer that improves the adhesion of the barrier layer 4 laminated on the transparent substrate film 2. The primer layer 3 is disposed on one thickness-wise side of the transparent substrate film 2 and on the other thickness-wise side of the barrier layer 4. That is, the primer layer 3 is disposed between the transparent substrate film 2 and the barrier layer 4. Specifically, as shown in FIG. 1, the primer layer 3 is disposed on one thickness-wise surface of the transparent substrate film 2 (one thickness-wise surface of the cured resin layer 22). That is, the primer layer 3 contacts the transparent substrate film 2 (cured resin layer 22).

[0047] Examples of materials for the primer layer 3 include metals such as nickel, chromium, indium, aluminum, tin, gold, silver, platinum, zinc, titanium, tungsten, zirconium, and palladium, alloys of two or more of these metals, and oxides of these metals. Examples of materials for the primer layer 3 include semi-metals such as silicon and oxides of these metals.

[0048] Examples of metal oxides include indium-containing conductive oxides, antimony-containing conductive oxides, and zinc-containing conductive oxides. Examples of indium-containing conductive oxides include indium tin oxide (ITO), indium zinc oxide (IZO), indium gallium oxide (IGO), and indium gallium zinc oxide (IGZO). Examples of antimony-containing conductive oxides include antimony tin oxide (ATO). Examples of zinc-containing conductive oxides include zinc aluminum oxide (AZO).

[0049] The material of the primer layer 3 is preferably an inorganic oxide containing at least one element selected from the group consisting of silicon, indium, aluminum, tin, titanium, and zirconium. From the viewpoint of adhesion to both the transparent substrate film 2 and the barrier layer 4 laminated on the primer layer 3, the material of the primer layer 3 is more preferably a metal oxide, and further preferably an indium tin composite oxide (ITO). In other words, the primer layer 3 is more preferably a metal oxide layer, and further preferably an ITO layer.

[0050] In ITO as a material for the primer layer, the content of tin oxide relative to the total amount of indium oxide and tin oxide is, for example, 1 mass% to 50 mass%, preferably 3 mass% to 45 mass%, more preferably 5 mass% to 40 mass%, and even more preferably 10 mass% to 35 mass%.

[0051] In ITO as a material for the primer layer, the content of tin oxide relative to the total amount of indium oxide and tin oxide is, for example, 1 mass% or more, preferably 3 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, and for example, 50 mass% or less, preferably 45 mass% or less, more preferably 40 mass% or less, even more preferably 35 mass% or less.

[0052] The thickness of the primer layer 3 is, for example, 0.1 nm to 30.0 nm, preferably 0.5 nm to 20.0 nm, more preferably 1.0 nm to 15.0 nm, still more preferably 2.0 nm to 10.0 nm, and particularly preferably 3.0 nm to 8.0 nm.

[0053] The thickness of the primer layer 3 is, for example, 0.1 nm or more, preferably 0.5 nm or more, more preferably 1.0 nm or more, even more preferably 2.0 nm or more, particularly preferably 3.0 nm or more, and for example, 30.0 nm or less, preferably 20.0 nm or less, more preferably 15.0 nm or less, even more preferably 10.0 nm or less, particularly preferably 8.0 nm or less.

[0054] When the thickness of the primer layer 3 is within the above range, the adhesive strength between the transparent substrate film 2 and the barrier layer 4 laminated on the primer layer 3 can be ensured.

[0055] <Barrier layer> The barrier layer 4 is a layer that improves the water vapor barrier property of the barrier film 1, and can therefore suppress discoloration of the polarizing plate under heating and humidifying conditions. The barrier layer 4 is the uppermost layer of the barrier film 1. The barrier layer 4 is disposed on one side in the thickness direction of the transparent substrate film 2. Specifically, the barrier layer 4 is disposed on one surface in the thickness direction of the primer layer 3. In other words, the barrier layer 4 is in contact with the primer layer 3.

[0056] The barrier layer 4 comprises at least one silicon oxide layer 42 and an antifouling layer 43 disposed on one side in the thickness direction of the silicon oxide layer 42. The barrier layer 4 preferably comprises an alternating laminate composed of at least one niobium oxide layer 41 and at least one silicon oxide layer 42, and an antifouling layer disposed on one surface in the thickness direction of the alternating laminate. Specifically, as shown in Fig. 1, the barrier layer 4 comprises, in order in the thickness direction, an alternating laminate composed of a niobium oxide layer 41a (first layer), a silicon oxide layer 42a (second layer), a niobium oxide layer 41b (third layer), and a silicon oxide layer 42b (fourth layer), and the antifouling layer 43.

[0057] The niobium oxide layer 41a (first layer) is in contact with the primer layer 3. The niobium oxide layer 41a (first layer) is in contact with the silicon oxide layer 42a (second layer). The silicon oxide layer 42a (second layer) is in contact with the niobium oxide layer 41b (third layer). The niobium oxide layer 41b (third layer) is in contact with the silicon oxide layer 42b (fourth layer).

[0058] The niobium oxide layer 41 is a layer made of niobium oxide, and the silicon oxide layer 42 is a layer made of silicon oxide.

[0059] The niobium oxide layer 41 is a layer having a relatively high refractive index, and the silicon oxide layer 42 is a layer having a relatively low refractive index.

[0060] In such an alternate laminate configuration, the reflected light intensity is attenuated by interference between reflected light at multiple interfaces in the niobium oxide layer 41 and the silicon oxide layer 42. Such interference can be realized by adjusting the optical film thickness (the product of the refractive index and the thickness of the film) of the niobium oxide layer 41 and the silicon oxide layer 42.

[0061] The refractive index of the niobium oxide layer 41 at a wavelength of 550 nm is 2.33.

[0062] The niobium oxide layer 41a (first layer) has a thickness of, for example, 1 nm to 50 nm, preferably 5 nm to 30 nm, and more preferably 8 nm to 20 nm.

[0063] The niobium oxide layer 41a (first layer) has a thickness of, for example, 1 nm or more, preferably 5 nm or more, more preferably 8 nm or more, and for example, 50 nm or less, preferably 30 nm or less, more preferably 20 nm or less.

[0064] The niobium oxide layer 41b (third layer) has a thickness of, for example, 5 nm to 200 nm, preferably 10 nm to 100 nm, more preferably 15 nm to 60 nm, and still more preferably 20 nm to 40 nm.

[0065] The thickness of the niobium oxide layer 41b (third layer) is, for example, 5 nm or more, preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm or more, and for example, 200 nm or less, preferably 100 nm or less, more preferably 60 nm or less, even more preferably 40 nm or less.

[0066] The total thickness of the niobium oxide layer 41 is, for example, 1 nm to 300 nm, preferably 3 nm to 200 nm, and more preferably 5 nm to 100 nm.

[0067] The total thickness of the niobium oxide layer 41 is, for example, 1 nm or more, preferably 3 nm or more, more preferably 5 nm or more, and for example, 300 nm or less, preferably 200 nm or less, more preferably 100 nm or less.

[0068] When the alternate laminate has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the thickness of the niobium oxide layer 41a (first layer) is preferably thinner than the thickness of the niobium oxide layer 41b (third layer).

[0069] When the alternating laminate has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the ratio of the thickness of the niobium oxide layer 41a (first layer) to the total thickness of the niobium oxide layers 41 is, for example, 5% to 50%, preferably 15% to 45%, more preferably 20% to 42%, and even more preferably 25% to 40%.

[0070] When the alternating laminate has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the ratio of the thickness of the niobium oxide layer 41a (first layer) to the total thickness of the niobium oxide layers 41 is, for example, 5% or more, preferably 15% or more, more preferably 20% or more, even more preferably 25% or more, and for example, less than 50%, preferably 45% or less, more preferably 42% or less, and even more preferably 40% or less.

[0071] When the alternating laminate has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the ratio of the thickness of the niobium oxide layer 41b (third layer) to the total thickness of the niobium oxide layers 41 is, for example, 50% to 95%, preferably 55% to 85%, more preferably 58% to 80%, and even more preferably 60% to 75%.

[0072] When the alternating laminate has a niobium oxide layer 41a (first layer) and a niobium oxide layer 41b (third layer), the ratio of the thickness of the niobium oxide layer 41b (third layer) to the total thickness of the niobium oxide layers 41 is, for example, 50% or more, preferably 55% or more, more preferably 58% or more, even more preferably 60% or more, and for example, 95% or less, preferably 85% or less, more preferably 80% or less, and even more preferably 75% or less.

[0073] The refractive index of the silicon oxide layer 42 at a wavelength of 550 nm is 1.46.

[0074] The silicon oxide layer 42a (second layer) has a thickness of, for example, 1 nm to 300 nm, preferably 10 nm to 200 nm, and more preferably 20 nm to 150 nm.

[0075] The silicon oxide layer 42a (second layer) has a thickness of, for example, 1 nm or more, preferably 10 nm or more, more preferably 20 nm or more, and for example, 300 nm or less, preferably 200 nm or less, more preferably 150 nm or less.

[0076] The silicon oxide layer 42b (fourth layer) has a thickness of, for example, 10 nm to 300 nm, preferably 30 nm to 200 nm, more preferably 50 nm to 150 nm, and still more preferably 70 nm to 120 nm.

[0077] The thickness of the silicon oxide layer 42b (fourth layer) is, for example, 10 nm or more, preferably 30 nm or more, more preferably 50 nm or more, even more preferably 70 nm or more, and for example, 300 nm or less, preferably 200 nm or less, more preferably 150 nm or less, even more preferably 120 nm or less.

[0078] The total thickness of the silicon oxide layer 42 is in the range of, for example, 20 nm to 500 nm, preferably 50 nm to 300 nm, more preferably 80 nm to 200 nm, and still more preferably 100 nm to 150 nm.

[0079] The total thickness of the silicon oxide layer 42 is, for example, 20 nm or more, preferably 50 nm or more, more preferably 80 nm or more, even more preferably 100 nm or more, and for example, 500 nm or less, preferably 300 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less.

[0080] When the alternate stack has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the thickness of the silicon oxide layer 42a (second layer) is preferably thinner than the thickness of the silicon oxide layer 42b (fourth layer).

[0081] When the alternating laminate has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the ratio of the thickness of the silicon oxide layer 42a (second layer) to the total thickness of the silicon oxide layers 42 is, for example, 1% to 50%, preferably 10% to 45%, more preferably 15% to 40%, and even more preferably 20% to 35%.

[0082] When the alternating laminate has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the ratio of the thickness of the silicon oxide layer 42a (second layer) to the total thickness of the silicon oxide layers 42 is, for example, 1% or more, preferably 10% or more, more preferably 15% or more, even more preferably 20% or more, and for example, less than 50%, preferably 45% or less, more preferably 40% or less, and even more preferably 35% or less.

[0083] When the alternating laminate has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the ratio of the thickness of the silicon oxide layer 42b (fourth layer) to the total thickness of the silicon oxide layers 42 is, for example, 50% to 99%, preferably 55% to 90%, more preferably 60% to 85%, and even more preferably 65% ​​to 80%.

[0084] When the alternating laminate has a silicon oxide layer 42a (second layer) and a silicon oxide layer 42b (fourth layer), the ratio of the thickness of the silicon oxide layer 42b (fourth layer) to the total thickness of the silicon oxide layers 42 is, for example, 50% or more, preferably 55% or more, more preferably 60% or more, even more preferably 65% ​​or more, and for example, 99% or less, preferably 90% or less, more preferably 85% or less, and even more preferably 80% or less.

[0085] The total thickness of the alternate laminate is, for example, 50 nm to 800 nm, preferably 80 nm to 500 nm, more preferably 100 nm to 400 nm, still more preferably 120 nm to 300 nm, and particularly preferably 130 nm to 250 nm.

[0086] The total thickness of the alternating laminate is, for example, 50 nm or more, preferably 80 nm or more, more preferably 100 nm or more, even more preferably 120 nm or more, particularly preferably 130 nm or more, and for example, 800 nm or less, preferably 500 nm or less, more preferably 400 nm or less, even more preferably 300 nm or less, particularly preferably 250 nm or less.

[0087] If the total thickness of the alternate laminate is equal to or greater than the lower limit, the reflected light intensity can be attenuated.If the total thickness of the alternate laminate is equal to or less than the upper limit, cracking of the alternate laminate can be suppressed.

[0088] The ratio of the thickness (total thickness) of the niobium oxide layer 41 to the total thickness of the alternate laminate is, for example, 1% to 80%, preferably 3% to 60%, more preferably 10% to 40%, even more preferably 15% to 35%, and particularly preferably 20% to 30%.

[0089] The ratio of the thickness (total thickness) of the niobium oxide layer 41 to the total thickness of the alternating laminate is, for example, 1% or more, preferably 3% or more, more preferably 10% or more, even more preferably 15% or more, particularly preferably 20% or more, and for example, 80% or less, preferably 60% or less, more preferably 40% or less, even more preferably 35% or less, and particularly preferably 30% or less.

[0090] The ratio of the thickness (total thickness) of the silicon oxide layer 42 to the total thickness of the alternate laminate is, for example, 20% to 99%, preferably 40% to 97%, more preferably 60% to 90%, even more preferably 65% ​​to 85%, and particularly preferably 70% to 80%.

[0091] The ratio of the thickness (total thickness) of the silicon oxide layer 42 to the total thickness of the alternating laminate is, for example, 20% or more, preferably 40% or more, more preferably 60% or more, even more preferably 65% ​​or more, particularly preferably 70% or more, and for example, 99% or less, preferably 97% or less, more preferably 90% or less, even more preferably 85% or less, particularly preferably 80% or less.

[0092] One surface in the thickness direction of the alternating laminate (the surface in contact with the antifouling layer 43) may be subjected to a surface modification treatment. Examples of the surface modification treatment include a corona treatment, a plasma treatment, an ozone treatment, a primer treatment, a glow treatment, and a coupling agent treatment.

[0093] The surface roughness Ra (arithmetic mean surface roughness) of one surface in the thickness direction of the alternate laminate (the surface in contact with the antifouling layer 43) is in the range of, for example, 0.5 nm to 10 nm, or preferably 0.8 nm to 8 nm.

[0094] The surface roughness Ra (arithmetic mean surface roughness) of one surface in the thickness direction of the alternate laminate (the surface in contact with the antifouling layer 43) is, for example, 0.5 nm or more, preferably 0.8 nm or more, and for example, 10 nm or less, preferably 8 nm or less.

[0095] The surface roughness Ra can be determined from an image of a 1 μm square observed with an AFM (atomic force microscope).

[0096] The density of the silicon oxide layer 42 closest to the antifouling layer 43 in the thickness direction is, for example, 2.35 g / cm 3 ~2.50g / cm 3 , preferably 2.35 g / cm 3 ~2.47g / cm 3 , more preferably 2.37 g / cm 3 ~2.45g / cm 3 , and more preferably 2.39 g / cm 3 ~2.45g / cm 3 It is also preferable that the other silicon oxide layers 42 have a similar density.

[0097] The density of the silicon oxide layer 42 closest to the antifouling layer 43 in the thickness direction is 2.35 g / cm 3 More preferably, 2.37 g / cm 3 More preferably, 2.39 g / cm 3 or more, for example, 2.50 g / cm 3 Less than or equal to 2.47 g / cm 3 Less than or equal to 2.45 g / cm 3 The following is the result.

[0098] When the density of the silicon oxide layer 42 closest to the antifouling layer 43 in the thickness direction is equal to or greater than the above-mentioned lower limit, the water vapor barrier properties of the barrier film 1 can be improved, and discoloration of the polarizing plate under heated and humidified conditions can be suppressed.

[0099] The density of the niobium oxide layer 41 is, for example, 4.00 g / cm 3 ~5.00g / cm 3 It is.

[0100] The density of the niobium oxide layer 41 is, for example, 4.00 g / cm 3 or more, for example, 5.00 g / cm 3 The following is the result.

[0101] The antifouling layer 43 is a layer that prevents contamination from the external environment and facilitates the removal of attached contaminants. The antifouling layer 43 also has water vapor barrier properties. The antifouling layer 43 is the uppermost layer of the barrier film 1.

[0102] An organic fluorine compound having an end structure (end structure E) represented by the chemical formula CF3OCF2- is used as the material for the antifouling layer 43. That is, the antifouling layer 43 contains an organic fluorine compound having end structure E. As such an organic fluorine compound, an alkoxysilane compound having a perfluoropolyether skeleton is preferably used. As an alkoxysilane compound having end structure E and a perfluoropolyether skeleton, for example, a compound represented by the following general formula (1) can be mentioned.

[0103] CF3-OCF2-R1-X-(CH2) m -Si(OR2)3(1)

[0104] R1 represents a structure containing at least one repeating structure of a perfluoropolyether (PFPE) group, and preferably represents a structure containing two repeating structures of a PFPE group. Examples of the repeating structure of a PFPE group include a repeating structure of a linear PFPE group and a repeating structure of a branched PFPE group. Examples of the repeating structure of a linear PFPE group include -(OC n F 2n ) p - (wherein n is an integer of 1 or more and 20 or less, and p is an integer of 1 or more and 100 or less; the same applies below). Examples of the repeating structure of the branched PFPE group include -(OC(CF3)2) p - and -(OCF2CF(CF3)CF2) p The repeating structure of the PFPE group is preferably a repeating structure of a linear PFPE group, more preferably -(OCF2) p -and-(OC2F4) pR2 is, for example, an alkyl group having 1 to 4 carbon atoms, and preferably a methyl group. X is, for example, an ether group, a carbonyl group, an amino group, or an amide group, and preferably an ether group. m is, for example, an integer of 1 to 20, preferably 1 to 10, and more preferably 1 to 5.

[0105] The alkoxysilane compounds having a perfluoropolyether skeleton can be used alone or in combination of two or more kinds.

[0106] If the material of the antifouling layer 43 contains an alkoxysilane compound having a perfluoropolyether skeleton, the antifouling function of the antifouling layer 43 can be improved.

[0107] The water contact angle (pure water contact angle) of the outer surface (exposed surface) of the anti-fouling layer 43 is, for example, 110° to 130°, preferably 111° to 130°, more preferably 112° to 130°, even more preferably 113° to 130°, and particularly preferably 114° to 130°.

[0108] The water contact angle (pure water contact angle) of the outer surface (exposed surface) of the anti-fouling layer 43 is, for example, 110° or more, preferably 111° or more, more preferably 112° or more, even more preferably 113° or more, particularly preferably 114° or more, and for example, 130° or less.

[0109] When the water contact angle on the outer surface of the antifouling layer 43 is equal to or greater than the above lower limit, the antifouling layer 43 has high antifouling properties.

[0110] The water contact angle can be determined by forming a water droplet (pure water droplet) with a diameter of 2 mm or less on the outer surface of the antifouling layer 43 and measuring the contact angle of the water droplet with the outer surface of the antifouling layer 43. The water contact angle of the outer surface of the antifouling layer 43 can be adjusted by, for example, the composition of the antifouling layer 43, the roughness of the outer surface, and the composition of other layers.

[0111] The antifouling layer 43 has a thickness of, for example, 1 nm to 100 nm, preferably 3 nm to 50 nm, more preferably 5 nm to 20 nm, and still more preferably 6 nm to 12 nm.

[0112] The thickness of the anti-fouling layer 43 is, for example, 1 nm or more, preferably 3 nm or more, more preferably 5 nm or more, even more preferably 6 nm or more, and for example, 100 nm or less, preferably 50 nm or less, more preferably 20 nm or less, even more preferably 12 nm or less.

[0113] It is preferable that the antifouling layer 43 has a small difference in refractive index from a layer with which it is in contact. Specifically, when the antifouling layer 43 is in contact with the silicon oxide layer 42, the refractive index of the antifouling layer 43 is, for example, 1.6 or less, preferably 1.55 or less.

[0114] The thickness of the barrier film 1 is, for example, 5 μm to 300 μm, preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, still more preferably 30 μm to 170 μm, and particularly preferably 50 μm to 150 μm.

[0115] The thickness of the barrier film 1 is, for example, 5 μm or more, preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, particularly preferably 50 μm or more, and for example, 300 μm or less, preferably 250 μm or less, more preferably 200 μm or less, even more preferably 170 μm or less, and particularly preferably 150 μm or less.

[0116] The reflectance of the barrier film 1 is, for example, 0.0% to 8.0%, preferably 0.0% to 5.0%, more preferably 0.0% to 4.0%, still more preferably 0.0% to 2.0%, and particularly preferably 0.0% to 1.0%.

[0117] The reflectance of the barrier film 1 is, for example, 0.0% or more, and, for example, 8.0% or less, preferably 5.0% or less, more preferably 4.0% or less, even more preferably 2.0% or less, and particularly preferably 1.0% or less.

[0118] The reflectance of the barrier film 1 can be measured using an ultraviolet, visible, and infrared spectrophotometer.

[0119] 2. Barrier film manufacturing method The method for producing a barrier film of the present invention will be described with reference to FIGS. 2A to 2E.

[0120] The method for producing the barrier film 1 includes, for example, a preparation step (FIG. 2A) of preparing a transparent resin film 21, a cured resin layer formation step (FIG. 2B) of forming a cured resin layer 22 on the transparent resin film 21, a primer layer formation step (FIG. 2C) of forming a primer layer 3 on the cured resin layer 22, an alternate laminate formation step (FIG. 2D) of forming an alternate laminate of a niobium oxide layer 41 and a silicon oxide layer 42 on the primer layer 3, and an antifouling layer formation step (FIG. 2E) of forming an antifouling layer 43 on the alternate laminate. The primer layer formation step and the alternate laminate formation step are sequentially performed using an apparatus Z as shown in FIG. 5.

[0121] <Preparation process> In the preparation step, as shown in FIG. 2A, a transparent resin film 21 is prepared.

[0122] <Cured resin layer formation process> 2B, in the cured resin layer forming step, a cured resin layer 22 is formed on one surface in the thickness direction of a transparent resin film 21. Specifically, the above-mentioned curable resin composition is applied to one surface in the thickness direction of the transparent resin film 21 to form a coating film, and then the coating film is cured to form the cured resin layer 22.

[0123] When the curable resin composition contains a solvent, the coating film on the transparent resin film 21 is dried after the curable resin composition is applied.

[0124] The drying temperature is, for example, 50° C. to 120° C. The drying time is, for example, 10 seconds to 10 minutes.

[0125] When the curable resin composition contains an ultraviolet-curable resin, the coating film on the transparent resin film 21 is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a high-pressure mercury lamp and an LED light. The cumulative irradiation amount of ultraviolet light is, for example, 100 mJ / cm. 2 ~500mJ / cm 2 It is.

[0126] In this manner, a transparent substrate film 2 having the cured resin layer 22 on one surface in the thickness direction of the transparent resin film 21 is obtained. In this embodiment, a roll of the transparent substrate film 2 is prepared. Specifically, the transparent substrate film 2 is wound so that the surface of the transparent substrate film 2 on the cured resin layer 22 side faces inward in the roll radial direction.

[0127] [Device Z] In the method for producing the barrier film 1, a primer layer forming step and an alternating laminate forming step are then carried out in sequence while the transparent substrate film 2 is transported as a workpiece film W by a roll-to-roll method under a reduced pressure atmosphere. A magnetron sputtering deposition apparatus Z, which is an example of an apparatus for carrying out the primer layer forming step and the alternating laminate forming step, will be described with reference to Fig. 5.

[0128] As shown in FIG. 5, the apparatus Z includes a transfer section P1 and a film forming section P2.

[0129] The conveying section P1 includes a conveying casing 51, a delivery roll 52, a take-up roll 53, a guide roll 54, and a vacuum pump 55.

[0130] The transport casing 51 has a generally box-like shape extending along the transport direction and accommodates a delivery roll 52, a take-up roll 53, and a guide roll .

[0131] The feed roll 52 and the take-up roll 53 are disposed at the upstream end and downstream end, respectively, of the transport casing 51 in the transport direction. A roll of the transparent substrate film 2 is attached to the feed roll 52 as the workpiece film W. The take-up roll 53 is a roll for taking up the workpiece film W. A plurality of guide rolls 54 are disposed between the feed roll 52 and the take-up roll 53. The plurality of guide rolls 54 are disposed so as to wind the transparent substrate film 2 around the film-forming roll 63.

[0132] The vacuum pump 55 is provided in the conveyor casing 51 .

[0133] The film forming section P2 includes a film forming casing 61, a film forming roll 63, and a plurality of magnetron plasma units 64.

[0134] The film formation casing 61 is continuous with the transport casing 51 and constitutes a vacuum chamber together with the transport casing 51. The film formation casing 61 has a substantially box shape. The film formation casing 61 has a plurality of partition walls 62. The plurality of partition walls 62 extend toward the film formation roll 63. The film formation casing 61 is provided with a sputtering gas supply device (not shown). The film formation casing 61 houses the film formation roll 63 and a plurality of magnetron plasma units 64.

[0135] The film-forming roll 63 has an axis extending along the width direction of the transparent substrate film 2, which is perpendicular to the transport direction and thickness direction of the transparent substrate film 2.

[0136] The magnetron plasma units 64 are disposed facing each other on the radially outer side of the film-forming roll 63. The magnetron plasma units 64 are disposed along the circumferential direction of the film-forming roll 63 at intervals from each other.

[0137] Circumferentially adjacent magnetron plasma units 64 are separated by partition walls 62. The space separated by partition walls 62 constitutes a film formation chamber R. The film formation chamber R is separated into a plurality of chambers (e.g., a first film formation chamber R1, a second film formation chamber R2, a third film formation chamber R3, and a fourth film formation chamber R4) within a film formation casing 61 (vacuum chamber). One magnetron plasma unit 64 is provided in one film formation chamber R. Each of the plurality of magnetron plasma units 64 includes a plasma casing 71, a first unit 72, and a second unit 73, as shown in FIG. 6.

[0138] The plasma casing 71 has a generally box-like shape with one side open toward the film-forming roll 63. The plasma casing 71 extends along the axis of the film-forming roll 63. The plasma casing 71 houses a first unit 72 and a second unit 73. The first unit 72 and the second unit 73 are disposed adjacent to each other at an interval along the circumferential direction of the film-forming roll 63. The first unit 72 and the second unit 73 face the film-forming roll 63 through the opening of the plasma casing 71.

[0139] The first unit 72 and the second unit 73 have the same configuration except for the rotation direction of the rotary target 74 (described later). Therefore, the first unit 72 will be described in detail and the second unit 73 will be briefly described with reference to Figures 6 to 8. Note that Figure 7 shows the magnet unit 75 of the first magnetron plasma unit 64 used to form the primer layer 3, and Figure 8 shows the magnet unit 75 of the second magnetron plasma unit 64 used to form the niobium oxide layer 41 and the silicon oxide layer 42.

[0140] As shown in FIG. 6, the first unit 72 includes a rotary target 74 and a magnet unit 75.

[0141] The rotary target 74 has a cylindrical shape and has an axis AL (center in cross-sectional view, see Figs. 7 and 8) parallel to the axis of the film-forming roll 63. The rotary target 74 is, for example, rotatable (movable around) in a direction opposite to the rotation direction of the film-forming roll 63. The rotary target 74 is electrically connected to a cathode source (not shown), and can thereby act as a cathode. In addition, a target material is laminated on the outer circumferential surface of the rotary target 74. Examples of the target material include the material of the primer layer 3 described above, niobium (the material of the niobium oxide layer 41), and silicon (the material of the silicon oxide layer 42).

[0142] The magnet unit 75 is housed radially inside the rotary target 74. The magnet unit 75 includes a fixed member 80, two first magnets 81, and two second magnets 82, as shown in FIGS.

[0143] The fixing member 80 has a narrow plate shape extending in the axial direction of the film-forming roll 63, and is called a yoke. One surface in the thickness direction of the fixing member 80 (one main surface 83) and the other surface in the thickness direction (the other main surface) are both flat surfaces. One main surface 83 faces the film-forming roll 63. The other main surface is parallel to the one main surface. Examples of materials for the fixing member 80 include metals such as iron.

[0144] Each of the two first magnets 81 and the two second magnets 82 has a rectangular prism shape extending along the axial direction of the film-forming roll 63. The two first magnets 81 and the two second magnets 82 are fixed to one main surface 83 of the fixed member 80. The two first magnets 81 and the two second magnets 82 are disposed adjacent to each other in the width direction of the fixed member 80. Specifically, the two first magnets 81 and the two second magnets 82 are in contact with each other in the width direction.

[0145] The two first magnets 81 and the two second magnets 82 include a first magnetic pole portion 91, a second magnetic pole portion 92, a third magnetic pole portion 93, and a fourth magnetic pole portion 94 when viewed in a cross-sectional view along the width and thickness directions of the fixed member 80 (corresponding to a direction perpendicular to the axis of the rotary target 74).

[0146] The first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are arranged in sequence along one circumferential direction (the rotation direction of the rotary target 74). The first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are arranged in sequence toward one width direction side of the fixed member 80 so as to be in contact with each other.

[0147] The second magnetic pole portion 92 and the third magnetic pole portion 93 are formed from the two first magnets 81. The second magnetic pole portion 92 and the third magnetic pole portion 93 have, for example, an N pole. The first magnetic pole portion 91 and the fourth magnetic pole portion 94 are formed from, for example, the second magnet 82. The first magnetic pole portion 91 and the fourth magnetic pole portion 94 have, for example, an S pole.

[0148] In a cross-sectional view, the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 each have the same generally rectangular shape. In a cross-sectional view, the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 each have a generally rectangular shape having a fixed side fixed to one main surface 83 of the fixed member 80, an opposing side located opposite the fixed side, and two side sides connecting both end edges thereof.

[0149] The fixed sides of each of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are disposed on one main surface 83 of the fixed member 80. The opposite sides of each of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are parallel to the one main surface 83 of the fixed member 80. The opposite sides of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are continuous along the width direction, and specifically, are flush (form one flat surface).

[0150] The thickness direction length and width direction length of each of the first magnetic pole part 91, the second magnetic pole part 92, the third magnetic pole part 93, and the fourth magnetic pole part 94 differ depending on the sputtering angle that is set.

[0151] In the magnet unit 75 of the first magnetron plasma unit 64 shown in FIG. 7, the ratio (D / L) of the thickness direction length and width direction length of each of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94, i.e., the ratio of the distance D (length of the side) between the opposite side and the fixed side to the length L of the opposite side, is, for example, 0.8 to 1.2, preferably 0.9 to 1.1, and more preferably 1.0.

[0152] In the magnet unit 75 of the first magnetron plasma unit 64 shown in FIG. 7, the ratio (D / L) of the thickness direction length and width direction length of each of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94, i.e., the ratio of the separation distance D (length of the side) between the opposite side and the fixed side to the length L of the opposite side, is, for example, 0.8 or more, preferably 0.9 or more, and for example, 1.2 or less, preferably 1.1 or less.

[0153] In the magnet unit 75 of the first magnetron plasma unit 64 shown in FIG. 7, the thickness direction length and width direction length of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93, and the fourth magnetic pole portion 94 are preferably equal to each other.

[0154] If the ratio (D / L) is within the above range, the sputtering angle (angle θ) is as follows.

[0155] 7, in a cross-sectional view, the magnetization directions of the second magnetic pole portion 92 and the third magnetic pole portion 93 are parallel to the thickness direction of the fixed member 80 (perpendicular to the width direction of the fixed member 80), and the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 are parallel to the width direction of the fixed member 80 (perpendicular to the thickness direction of the fixed member 80). If the magnetization directions are as described above, the following sputtering angle (angle θ) is obtained.

[0156] The sputtering angle (angle θ) in the magnet unit 75 of the first magnetron plasma unit 64 shown in FIG. 7 is, for example, 35 degrees to 50 degrees, preferably 37 degrees to 48 degrees, more preferably 39 degrees to 46 degrees, and even more preferably 40 degrees to 45 degrees.

[0157] The sputtering angle (angle θ) in the magnet unit 75 of the first magnetron plasma unit 64 shown in FIG. 7 is, for example, 35 degrees or more, preferably 37 degrees or more, more preferably 39 degrees or more, even more preferably 40 degrees or more, and for example, 50 degrees or less, preferably 48 degrees or less, more preferably 46 degrees or less, even more preferably 45 degrees or less.

[0158] The sputtering angle is the angle θ shown below. The tangential component of the magnetic flux density is measured on the outer circumferential surface of the rotary target 74 in one circumferential direction of the rotary target. The angle θ formed by the line segment LS1 connecting the point MAX_P corresponding to the maximum tangential component of the magnetic flux density and the center of the rotary target 74, and the line segment LS2 connecting the point MIN_P corresponding to the minimum tangential component of the magnetic flux density and the center, is obtained. The angle θ is obtained, for example, by simulating a magnetic field using commercially available software.

[0159] Here, the tangential component of the magnetic flux density obtained by the above simulation will be described.

[0160] 7 and 8, in the first unit 72, a tunnel-shaped first magnetic field MF1 (drawn with a plurality of dots) is generated from the opposite side of the second magnetic pole portion 92 having an N pole toward the opposite side of the first magnetic pole portion 91 having an S pole. If the second magnetic pole portion 92 is an N pole and the first magnetic pole portion 91 is an S pole, the minimum of the magnetic flux density (i.e., the strongest value of the magnetic field on the negative side, MIN_P) can be obtained by measuring the tangential component of the magnetic flux density in one direction, which is the circumferential direction of the rotary target 74 and faces from the first magnetic pole portion 91 toward the second magnetic pole portion 92.

[0161] Also, a tunnel-shaped second magnetic field MF2 (drawn with multiple dots) is generated from the opposite side of the third magnetic pole portion 93 having an N pole toward the opposite side of the fourth magnetic pole portion 94 having an S pole. If the third magnetic pole portion 93 is an N pole and the fourth magnetic pole portion 94 is an S pole, then by measuring the tangential component of the magnetic flux density in one direction, from the third magnetic pole portion 93 toward the fourth magnetic pole portion 94, which is the circumferential direction of the rotary target 74, the maximum of the magnetic flux density (i.e., the strongest value of the magnetic field on the positive side, MAX_P) can be obtained.

[0162] The point MAX_P corresponding to the maximum tangential component of the magnetic flux density and the point MIN_P corresponding to the minimum tangential component are synonymous with the points corresponding to two maxima in the absolute value of the tangential component of the magnetic flux density.

[0163] The sputtering angle (angle θ) is the angle on the deposition roll 63 side of the angles formed by the above-mentioned two line segments LS1 and LS2.

[0164] In the magnet unit 75 of the first magnetron plasma unit 64 shown in Figure 7, the sputtering angle is such that, on the radial outside of the rotary target 74, the circumferential distance between the plasma corresponding to the maximum tangential component of the magnetic flux density and the plasma corresponding to the minimum tangential component of the magnetic flux density becomes large.

[0165] On the other hand, in the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 8, the ratio (D / L) of the thickness direction length and width direction length of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93 and the fourth magnetic pole portion 94, i.e., the ratio of the distance D (length of the side) between the opposite side and the fixed side to the length L of the opposite side, is, for example, 1.2 to 6.0, preferably 1.3 to 6.0, more preferably 1.5 to 6.0, even more preferably 1.6 to 6.0, and particularly preferably 1.7 to 6.0.

[0166] In the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 8, the ratio (D / L) of the thickness direction length and width direction length of the first magnetic pole portion 91, the second magnetic pole portion 92, the third magnetic pole portion 93 and the fourth magnetic pole portion 94, i.e., the ratio of the distance D (length of the side) between the opposite side and the fixed side to the length L of the opposite side, is, for example, 1.2 or more, preferably 1.3 or more, more preferably 1.5 or more, even more preferably 1.6 or more, particularly preferably 1.7 or more, and also, for example, 6.0 or less.

[0167] If the ratio (D / L) is within the above range, the sputtering angle (angle θ) is as follows.

[0168] 8 has a magnet unit 75 in which the magnetization directions of the second magnetic pole portion 92 and the third magnetic pole portion 93 are inclined in the thickness direction and width direction of the fixed member 80 in a cross-sectional view, and the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 are in a direction parallel to the width direction of the fixed member 80 (a direction perpendicular to the thickness direction of the fixed member 80). Note that the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 may also be inclined in the thickness direction and width direction of the fixed member 80.

[0169] Specifically, the magnetization directions of the second magnetic pole portion 92 and the third magnetic pole portion 93 are inclined in the thickness direction of the fixed member 80 toward the film depositing roll 63 so as to intersect with each other.

[0170] In addition, when the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 also incline in the thickness direction and width direction of the fixed member 80, the magnetization directions of the first magnetic pole portion 91 and the fourth magnetic pole portion 94 incline in directions that intersect with each other in the thickness direction of the fixed member 80 as they move away from the film-forming roll 63.

[0171] The magnetization directions of the second magnetic pole portion 92 and the third magnetic pole portion 93 cross each other, so that the magnetic flux on the surface of the rotary target 74 can be concentrated. As a result, the two tunnel-shaped magnetic fields approach each other, and have the following sputtering angle (angle θ). Specifically, the sputtering angle (angle θ) in the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 8 is smaller than the sputtering angle (angle θ) in the magnet unit 75 of the first magnetron plasma unit 64 shown in FIG. 7.

[0172] The sputtering angle (angle θ) in the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 8 is, for example, 10 degrees to 35 degrees, preferably 15 degrees to 34 degrees, more preferably 20 degrees to 33 degrees, and even more preferably 22 degrees to 32 degrees.

[0173] The sputtering angle (angle θ) in the magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 8 is, for example, 10 degrees or more, preferably 15 degrees or more, more preferably 20 degrees or more, even more preferably 22 degrees or more, and for example, 35 degrees or less, preferably 34 degrees or less, more preferably 33 degrees or less, even more preferably 32 degrees or less.

[0174] Furthermore, if the sputtering angle (angle θ) is within the above range, the distance in the circumferential direction between the plasma corresponding to the maximum tangential component of the magnetic flux density and the plasma corresponding to the minimum tangential component of the magnetic flux density becomes short on the radial outside of the rotary target 74. Therefore, it is possible to concentrate an area where the density of electrons emitted from the rotary target 74 is high. In other words, it is possible to increase the maximum of the magnetic flux density at the point MAX_P, and thus to increase the density of the layer to be formed. Furthermore, if the sputtering angle (angle θ) is equal to or greater than the above lower limit, it is possible to prevent the magnetic flux density from becoming excessively low. In other words, it is possible to reduce the minimum of the magnetic flux density at the point MIN_P, and it is possible to continuously generate plasma.

[0175] The material of the first magnet 81 and the second magnet 82 may be, for example, a permanent magnet such as a neodymium magnet.

[0176] As shown in FIG. 5, the second unit 73 includes a rotary target 74 that is rotatable in the same direction as the rotation direction of the film-forming roll 63, and the magnet unit 75 described above.

[0177] The second unit 73 has a similar configuration to the first unit 72.

[0178] <Primer layer formation process> Specifically, in the primer layer 3 formation process, the above-mentioned material for the primer layer 3 is deposited on one thickness-wise surface of the transparent substrate film 2 (one thickness-wise surface of the cured resin layer 22) by a sputtering method to form the primer layer 3.

[0179] In the sputtering method, a sputtering film-forming apparatus such as the above-mentioned apparatus Z, which can perform a film-forming process by a roll-to-roll method, is used. When a roll-to-roll sputtering film-forming apparatus is used in the primer layer forming step, the transparent base film 2 as the workpiece film W is run from the delivery roll 52 to the take-up roll 53, while the material of the primer layer 3 is formed on one surface in the thickness direction of the transparent base film 2 to form the primer layer 3. The running speed of the workpiece film W (transparent base film 2) is, for example, 0.5 to 10.0 m / min. In the primer layer forming step, a magnet unit 75 of the first magnetron plasma unit 64 shown in FIG. 7 is used.

[0180] In the sputtering method in the primer layer formation process, a sputter deposition apparatus having one deposition chamber may be used, or a sputter deposition apparatus having multiple deposition chambers (R1 to R4) arranged in sequence along the traveling path of the workpiece film W (transparent substrate film 2) as shown in Figure 5 may be used.

[0181] Specifically, in the sputtering method, a sputtering gas (inert gas) is introduced into the film-forming chamber R under vacuum conditions, while a negative voltage is applied to the target arranged on the outer circumferential surface of the rotary target 74 in the film-forming chamber R. This generates a glow discharge to ionize the gas atoms, and the gas ions collide with the target surface at high speed to eject the target material from the target surface, and the ejected target material is deposited on one side in the thickness direction of the workpiece film W (transparent substrate film 2). As the target material, for example, a sintered body of the material of the primer layer 3 described above is used.

[0182] Examples of the sputtering gas include argon, krypton, xenon, and mixed gases thereof, and preferably argon. The sputtering method is preferably a reactive sputtering method. In the reactive sputtering method, for example, oxygen as a reactive gas is introduced into the film formation chamber R in addition to the sputtering gas.

[0183] The ultimate vacuum in the deposition chamber R before sputter deposition is, for example, 1.5×10 -4 Pa or less.

[0184] In the reactive sputtering method, the volume ratio of oxygen gas to the total volume of the sputtering gas and oxygen gas (reactive gas) introduced into the film formation chamber R is, for example, 1 volume % to 30 volume %, preferably 3 volume % to 20 volume %, more preferably 5 volume % to 15 volume %, and even more preferably 7 volume % to 12 volume %.

[0185] The film formation temperature (the temperature of the transparent substrate film 2 when the primer layer 3 is formed) is, for example, -50.0°C to 30.0°C, preferably -30.0°C to 20.0°C, more preferably -20.0°C to 10.0°C, and still more preferably -15.0°C to 0.0°C.

[0186] The pressure in the film formation chamber R (the pressure in the film formation chamber when the sputtering gas and oxygen are introduced) is, for example, 0.01 Pa to 5.0 Pa, preferably 0.05 Pa to 1.0 Pa, more preferably 0.10 Pa to 0.50 Pa, and further preferably 0.15 Pa to 0.30 Pa.

[0187] Examples of the power source for applying a voltage to the target include a DC power source, an AC power source, an MF power source, and an RF power source. The power source may be a combination of an MF power source and an AC power source. The power source is preferably an MFAC power source.

[0188] The horizontal magnetic field strength on the target is, for example, 10 mT to 100 mT.

[0189] In this manner, the primer layer 3 is formed on one surface in the thickness direction of the transparent substrate film 2 .

[0190] <Alternate laminate formation process> In the alternate laminate formation step, specifically, a sputtering method is used to form an alternate laminate consisting of a niobium oxide layer 41 and a silicon oxide layer 42 on one surface in the thickness direction of the primer layer 3. Specifically, a niobium oxide layer 41a (first layer), a silicon oxide layer 42a (second layer), a niobium oxide layer 41b (third layer), and a silicon oxide layer 42b (fourth layer) are formed in this order on one surface in the thickness direction of the primer layer 3, thereby forming the alternate laminate.

[0191] In the sputtering method, a sputtering film-forming apparatus such as the above-mentioned apparatus Z, which can perform a film-forming process by a roll-to-roll method, is used. When a roll-to-roll sputtering film-forming apparatus is used in the alternate laminate forming process, the transparent base film 2 with the primer layer 3 as the work film W is made to run from the delivery roll 52 to the take-up roll 53, while the materials for the alternate laminate (specifically, niobium and silicon) are sequentially formed on one surface in the thickness direction of the primer layer 3 to form the alternate laminate. The running speed of the work film W (the transparent base film 2 with the primer layer 3) is, for example, 0.5 to 10.0 m / min. In the alternate laminate forming process, a magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 8 is used.

[0192] In the sputtering method used in the alternating laminate formation process, a sputtering deposition apparatus having multiple deposition chambers (R1 to R4) arranged in sequence along the running path of the workpiece film W (transparent substrate film 2 having a primer layer 3) as shown in Figure 5 is used to form the first to fourth layers in sequence.

[0193] Specifically, in the sputtering method, a sputtering gas (inert gas) is introduced into the film formation chamber R under vacuum conditions, while a negative voltage is applied to the target arranged on the outer circumferential surface of the rotary target 74 in the film formation chamber R. This generates a glow discharge to ionize the gas atoms, and the gas ions collide with the target surface at high speed, ejecting the target material from the target surface, and the ejected target material is deposited in order in the thickness direction. As the target material, niobium is used for the first and third layers, and silicon is used for the second and fourth layers.

[0194] Examples of the sputtering gas include argon, krypton, xenon, and mixed gases thereof, and preferably argon. The sputtering method is preferably a reactive sputtering method. In the reactive sputtering method, for example, oxygen as a reactive gas is introduced into the film formation chamber R in addition to the sputtering gas.

[0195] In the reactive sputtering method for forming the first and third layers, the volume ratio of oxygen gas to the total volume of the sputtering gas and oxygen gas (reactive gas) introduced into the film formation chambers (R1 and R3) is, for example, 0.5 vol.% to 20 vol.%, preferably 1 vol.% to 10 vol.%, more preferably 2 vol.% to 8 vol.%, and even more preferably 3 vol.% to 6 vol.%.

[0196] In the reactive sputtering method for forming the second and fourth layers, the volume ratio of oxygen gas to the total volume of the sputtering gas and oxygen gas (reactive gas) introduced into the film formation chambers (R2 and R4) is, for example, 5 volume % to 50 volume %, preferably 10 volume % to 40 volume %, more preferably 15 volume % to 30 volume %, and even more preferably 20 volume % to 25 volume %.

[0197] The pressure in the film formation chamber R (the pressure in the film formation chamber when the sputtering gas and oxygen are introduced) is, for example, 0.01 Pa to 5.0 Pa, preferably 0.05 Pa to 3.0 Pa, more preferably 0.10 Pa to 1.0 Pa, and further preferably 0.15 Pa to 0.80 Pa.

[0198] The ultimate vacuum level in the film formation chamber R before sputtering film formation, the film formation temperature (the temperature of the transparent substrate film 2 when each layer is formed), the power supply for applying voltage to the target, and the horizontal magnetic field strength above the target are the same as those in the primer layer formation process described above.

[0199] In this manner, an alternating laminate is formed on one surface of the primer layer 3 in the thickness direction.

[0200] <Anti-stain layer formation process> Specifically, in the antifouling layer forming step, the antifouling layer 43 is formed on one surface in the thickness direction of the alternate laminate by a dry coating method. Examples of the dry coating method include a vacuum deposition method, a sputtering method, and a CVD method, and preferably, the vacuum deposition method is used.

[0201] In the vacuum deposition method, the material of the antifouling layer 43 described above is dried and solidified, and used as a deposition source.

[0202] The deposition temperature is, for example, 150°C to 500°C, or preferably 200°C to 300°C.

[0203] In this way, an antifouling layer is formed on one surface in the thickness direction of the alternating laminate. That is, a barrier layer is formed on one surface in the thickness direction of the primer layer. The barrier layer includes a niobium oxide layer (first layer), a silicon oxide layer (second layer), a niobium oxide layer (third layer), a silicon oxide layer (fourth layer), and an antifouling layer in this order toward one side in the thickness direction.

[0204] In this manner, a barrier film is produced.

[0205] 3. Polarizing plate with barrier film With reference to FIG. 3, one embodiment of the barrier film-attached polarizing plate of the present invention will be described.

[0206] As shown in FIG. 3, the barrier film-attached polarizing plate 100 includes a barrier film 1 and a polarizing plate 10 disposed on the other side of the barrier film 1 in the thickness direction.

[0207] <Polarizing plate> 3, the polarizing plate 10 includes, for example, a protective film 11 and a polarizer 12. However, the configuration of the polarizing plate 10 is not limited thereto. Specifically, the polarizing plate 10 may include the protective films 11 on both sides of the polarizer 12 in the thickness direction, or may not include protective films on both sides, and may further include other functional layers (for example, a retardation layer, a conductive layer, and a resin substrate).

[0208] [Protective film] The protective film 11 may be, for example, a resin film. Examples of materials for the resin film include acrylic resin, polycarbonate resin, polyester resin, cycloolefin resin, and olefin resin, and preferably acrylic resin. The acrylic resin preferably includes a modified skeleton. Examples of the modified skeleton include a lactone ring structure, a maleic anhydride skeleton, an acrylonitrile skeleton, and a styrene skeleton. The (meth)acrylic resin refers to an acrylic resin and / or a methacrylic resin.

[0209] The moisture permeability of the protective film 11 is, for example, 0 g / m 2 / 24h~1000g / m 2 / 24h, preferably 10g / m 2 / 24h~500g / m 2 / 24h, more preferably 30g / m 2 / 24h~300g / m 2 / 24h, more preferably 50g / m 2 / 24h~200g / m 2 / 24h.

[0210] The moisture permeability of the protective film 11 is, for example, 0 g / m 2 / 24h or more, preferably 10g / m 2 / 24h or more, more preferably 30g / m 2 / 24h or more, more preferably 50g / m 2 / 24h or more, for example, 1000g / m 2 / 24h or less, preferably 500g / m 2 / 24h or less, more preferably 300g / m 2 / 24h or less, more preferably 200g / m 2 / 24h or less.

[0211] If the moisture permeability of the protective film 11 is within the above range, discoloration of the polarizing plate under heated and humidified conditions can be further suppressed.

[0212] The thickness of the protective film 11 is in the range of, for example, 1 μm to 300 μm, preferably 10 μm to 100 μm, and more preferably 20 μm to 80 μm.

[0213] The thickness of the protective film 11 is, for example, 1 μm or more, preferably 10 μm or more, more preferably 20 μm or more, and for example, 300 μm or less, preferably 100 μm or less, more preferably 80 μm or less.

[0214] [Polarizer] The polarizer 12 is, for example, a resin coating film containing a dichroic material. The resin coating film is formed by coating one side of a resin substrate 13 with a resin, as will be described in detail later.

[0215] The resin coating film is not particularly limited, and examples thereof include a coating film of polyvinyl alcohol (PVA) resin.

[0216] Examples of PVA resins include polyvinyl alcohol and ethylene-vinyl alcohol copolymers. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymers are obtained by saponifying ethylene-vinyl acetate copolymers. Polyvinyl alcohol may also be a derivative of polyvinyl alcohol. Examples of derivatives of polyvinyl alcohol include cation-modified polyvinyl alcohol, anion-modified polyvinyl alcohol, silanol-modified polyvinyl alcohol, and acetoacetyl-modified polyvinyl alcohol.

[0217] The PVA resin may be used alone or in combination of two or more kinds, and preferably, polyvinyl alcohol and acetoacetyl-modified polyvinyl alcohol are used in combination.

[0218] The saponification degree of the PVA resin is, for example, 85 mol % to 100 mol %, preferably 95.0 mol % to 99.95 mol %, and more preferably 99.0 mol % to 99.93 mol %. The saponification degree can be determined in accordance with JIS K6726-1994.

[0219] When the saponification degree of the PVA resin is within the above range, a polarizer having excellent durability can be obtained.

[0220] The average degree of polymerization of the PVA resin is, for example, 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K6726-1994.

[0221] Examples of the dichroic substance contained in the resin coating film include iodine and organic dyes, and preferably iodine. The dichroic substances can be used alone or in combination of two or more kinds.

[0222] The polarizer 12 may be, for example, a PVA resin coating film that is dyed with iodine and stretched (for example, uniaxially stretched). Note that, as will be described in detail later, the resin substrate 13 is dyed and stretched in a state where the PVA resin is applied thereto.

[0223] The polarizer 12 has a thickness of, for example, 1 μm to 20 μm, preferably 2 μm to 15 μm, and more preferably 3 μm to 10 μm.

[0224] The thickness of the polarizer 12 is, for example, 1 μm or more, preferably 2 μm or more, more preferably 3 μm or more, and for example, 20 μm or less, preferably 15 μm or less, more preferably 10 μm or less.

[0225] When the thickness of the polarizer 12 is within the above range, the barrier film-attached polarizing plate can be made thinner, and the reliability during humidification and heating can be improved.

[0226] The polarizer 12 exhibits absorption dichroism at any wavelength of, for example, 380 nm to 780 nm. The single transmittance of the polarizer 12 is, for example, 40.0% to 50.0%, preferably 41.0% to 48.0%, and more preferably 42.0% to 45.0%.

[0227] The single transmittance of the polarizer 12 is, for example, 40.0% or more, preferably 41.0% or more, more preferably 42.0% or more, and for example, 50.0% or less, preferably 48.0% or less, more preferably 45.0% or less.

[0228] The degree of polarization of the polarizer is, for example, 97.0% or more, preferably 99.0% or more, and more preferably 99.9% or more.

[0229] [Other functional layers] Examples of the other functional layers include a retardation layer, a conductive layer, and a transparent resin. The type, number, combination, arrangement position, and characteristics (e.g., optical characteristics such as refractive index characteristics, in-plane retardation, thickness direction retardation, and Nz coefficient) of the other functional layers can be appropriately set according to the purpose.

[0230] Examples of the retardation layer include a resin layer having a refractive index characteristic of nx>ny>nz, and a resin layer having a refractive index characteristic of nz>nx>ny. Examples of the material of such a retardation layer include the same resin as the material of the protective film 11 described above, and preferably include a cycloolefin resin and an olefin resin.

[0231] Although not shown, the polarizing plate 10 preferably includes a retardation layer on the surface opposite to the surface of the polarizer 12 that contacts the protective film 11. Specifically, although not shown, the polarizing plate 10 includes a first retardation layer having a refractive index characteristic of nx>ny>nz on the surface of the polarizer 12 opposite to the protective film 11, and a second retardation layer having a refractive index characteristic of nz>nx>ny on the surface of the first retardation layer opposite to the polarizer 12. The first retardation layer may also serve to protect the surface of the polarizer 12 opposite to the surface that contacts the protective film 11. When a retardation layer is provided, the angle between the slow axis of the retardation layer (if present) and the absorption axis of the polarizer can be appropriately set according to the purpose, the in-plane retardation of the retardation layer, the thickness direction retardation, the refractive index characteristics, and the like.

[0232] The conductive layer may be, for example, a metal oxide layer made of the same material as the above-mentioned primer layer 3. By providing a conductive layer, the barrier film-attached polarizing plate can be suitably used for an inner touch panel type input display device.

[0233] The other functional layers can be attached to the polarizer 12 via an adhesive, which will be described later.

[0234] The thickness of the polarizing plate 10 is, for example, 10 μm to 1000 μm, preferably 30 μm to 500 μm, and more preferably 40 μm to 300 μm.

[0235] The thickness of the polarizing plate 10 is, for example, 10 μm or more, preferably 30 μm or more, more preferably 40 μm or more, and for example, 1000 μm or less, preferably 500 μm or less, more preferably 300 μm or less.

[0236] The moisture content of the polarizing plate 10 is, for example, 0.5% by mass to 1.5% by mass, preferably 0.6% by mass to 1.5% by mass, and more preferably 0.8% by mass to 1.5% by mass.

[0237] The moisture content of the polarizing plate 10 is, for example, 0.5 mass % or more, preferably 0.6 mass % or more, more preferably 0.8 mass % or more, and for example, 1.5 mass % or less.

[0238] The moisture content of the polarizing plate 10 including the polarizer 12 made of a resin coating film is higher than that of a polarizing plate including a polarizer made of a resin film (e.g., a PVA film). When the polarizing plate 10 has such a high moisture content, the moisture absorption expansion of the polarizing plate 10 under heated and humidified conditions can be significantly suppressed. As a result, the dimensional change of the polarizing plate 10 under heated and humidified conditions (particularly the dimensional change in the absorption axis direction of the polarizer) is suppressed. However, discoloration of the polarizing plate 10 under heated and humidified conditions is likely to occur. Therefore, it is necessary to suppress discoloration of the polarizing plate 10 under heated and humidified conditions by providing a barrier film 1.

[0239] The thickness of the barrier film-attached polarizing plate 100 is, for example, 10 μm to 1000 μm, preferably 30 μm to 500 μm, and more preferably 50 μm to 300 μm.

[0240] The thickness of the barrier film-attached polarizing plate 100 is, for example, 10 μm or more, preferably 30 μm or more, more preferably 50 μm or more, and for example, 1000 μm or less, preferably 500 μm or less, more preferably 300 μm or less.

[0241] The moisture permeability of the barrier film-attached polarizing plate 100 under test conditions of a temperature of 40° C. and a humidity of 90% RH is, for example, 0.00 g / m2 day~100g / m 2 day, preferably 0.00g / m 2 day~10g / m 2 ·day, more preferably 0.00g / m 2 day~1.0g / m 2 ·day, more preferably 0.00 g / m 2 day~0.10g / m 2 day, particularly preferably 0.00 g / m 2 day~0.05g / m 2 day, most preferably 0.00 g / m 2 day~0.03g / m 2 ·day.

[0242] The moisture permeability of the barrier film-attached polarizing plate 100 under test conditions of a temperature of 40° C. and a humidity of 90% RH is, for example, 0.00 g / m 2 day or more, for example, 100g / m 2 ·day or less, preferably 10g / m 2 ·day or less, more preferably 1.0g / m 2 ·day or less, more preferably 0.10 g / m 2 day or less, particularly preferably 0.05 g / m 2 day or less, most preferably 0.03 g / m 2 ·day or less.

[0243] The moisture permeability of the barrier film-attached polarizing plate 100 under test conditions of a temperature of 40° C. and a humidity of 90% RH can be measured using a water vapor transmission rate measuring device.

[0244] Change in chromaticity of transmitted light Δb in a polarizing plate with a barrier film after 240 hours of heating and humidification at 60℃ and 90% RH * is, for example, 0.00 to 1.00, preferably 0.05 to 0.50, more preferably 0.10 to 0.30, and further preferably 0.10 to 0.28.

[0245] Change in chromaticity of transmitted light Δb in a polarizing plate with a barrier film after 240 hours of heating and humidification at 60℃ and 90% RH * is, for example, 0.00 or more, preferably 0.05 or more, more preferably 0.10 or more, and for example, 1.00 or less, preferably 0.50 or less, more preferably 0.30 or less, and even more preferably 0.28 or less.

[0246] Change in chromaticity of transmitted light Δb in a polarizing plate with a barrier film after 500 hours of heating and humidification at 60℃ and 90% RH * is, for example, 0.00 to 2.00, preferably 0.05 to 1.00, more preferably 0.10 to 0.80, and further preferably 0.10 to 0.50.

[0247] Change in chromaticity of transmitted light Δb in a polarizing plate with a barrier film after 500 hours of heating and humidification at 60℃ and 90% RH * is, for example, 0.00 or more, preferably 0.05 or more, more preferably 0.10 or more, and for example, 2.00 or less, preferably 1.00 or less, more preferably 0.80 or less, and even more preferably 0.50 or less.

[0248] The change in chromaticity of transmitted light, Δb * can be determined by the method described in the Examples below.

[0249] 4. Manufacturing method of polarizing plate with barrier film The method for producing a barrier film-attached polarizing plate of the present invention will be described with reference to FIGS. 4A to 4E.

[0250] A manufacturing method for a polarizing plate 100 with a barrier film includes, for example, a step of preparing a resin substrate 13 (FIG. 4A), a step of forming a coating film (polarizer 12) of polyvinyl alcohol resin on the resin substrate 13 (FIG. 4B), a step of attaching a protective film 11 onto the polarizer 12 via an adhesive (FIG. 4C), a step of removing the resin substrate 13 (FIG. 4D), and a step of attaching a barrier film 1 to the surface of the protective film 11 via an adhesive (FIG. 4E).

[0251] <Preparation process> In the preparation step, as shown in FIG. 4A, a resin base material 13 is prepared.

[0252] The resin substrate 13 has, for example, a film shape. The resin of the resin substrate 13 is not particularly limited, and examples thereof include the same resin as that of the transparent resin film 21, preferably a polyester resin, and more preferably a polyethylene terephthalate and a copolymer resin thereof.

[0253] The resin base material 13 has a thickness of, for example, 10 μm to 300 μm, preferably 30 μm to 200 μm, and more preferably 50 μm to 150 μm.

[0254] The resin substrate 13 has a thickness of, for example, 10 μm or more, preferably 30 μm or more, more preferably 50 μm or more, and for example, 300 μm or less, preferably 200 μm or less, more preferably 150 μm or less.

[0255] One surface of the resin substrate 13 (the surface on which the polarizer 12 is formed) may be subjected to a surface modification treatment such as corona treatment, plasma treatment, frame treatment, ozone treatment, primer treatment, glow treatment, saponification treatment, and treatment with a coupling agent.

[0256] <Polarizer formation process> In the polarizer formation step, as shown in FIG. 4B, a polarizer 12 is formed on one surface of a resin substrate 13 (on the surface-treated surface if the surface has been modified).

[0257] Specifically, an aqueous solution containing a polyvinyl alcohol resin is applied to one surface of the resin substrate 13. Then, the aqueous solution is dried to form a coating film of the polyvinyl alcohol resin.

[0258] Next, the resin substrate provided with a coating film of a polyvinyl alcohol resin (hereinafter referred to as a substrate with a PVA film) is dyed with iodine and stretched (for example, uniaxially stretched).

[0259] Dyeing with iodine is performed, for example, by immersing the substrate with the PVA film in an aqueous iodine solution.

[0260] The stretching includes, for example, immersing the laminate in an aqueous solution of boric acid and stretching it, and stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous solution of boric acid. The stretching ratio is, for example, 3 to 7 times. The stretching may be performed after dyeing or while dyeing. Alternatively, the stretching may be performed after dyeing.

[0261] If necessary, the PVA film-attached substrate may be subjected to an insolubilization treatment, a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like.

[0262] In this manner, the polarizer 12 is formed on one surface of the resin substrate 13 .

[0263] <Protective film attachment process> In the protective film attachment step, as shown in FIG. 4C, protective film 11 is attached to the surface of polarizer 12 opposite to the surface in contact with resin substrate 13 via an adhesive layer (not shown).

[0264] Specifically, an adhesive is applied to the surface (exposed surface) of the polarizer 12 opposite to the surface in contact with the resin substrate 13, and the protective film 11 is attached to the surface. Thereafter, the protective film 11 side is heated and irradiated with ultraviolet light to cure the adhesive.

[0265] The adhesive is not particularly limited as long as it is an adhesive that is commonly used in the optical field. Examples of the adhesive include a PVA adhesive and an activated energy ray curing adhesive, and preferably an acrylic adhesive.

[0266] The thickness of the adhesive layer (cured adhesive) between the polarizer 12 and the protective film 11 is in the range of, for example, 0.1 μm to 5.0 μm, or preferably 0.5 μm to 3.0 μm.

[0267] The thickness of the adhesive layer (cured adhesive) between the polarizer 12 and the protective film 11 is, for example, 0.1 μm or more, preferably 0.5 μm or more, and for example, 5.0 μm or less, preferably 3.0 μm or less.

[0268] If the adhesive is an acrylic adhesive, it is cured by ultraviolet irradiation. Examples of the light source for ultraviolet irradiation include a metal halide lamp. The cumulative irradiation amount of ultraviolet light is, for example, 500 mJ / cm. 2 ~2000mJ / cm 2 It is.

[0269] In this manner, the protective film 11 is attached to the surface of the polarizer 12 opposite to the surface in contact with the resin substrate 13 .

[0270] <Resin base material removal process> In the resin base material removing step, as shown in FIG. 4D, the resin base material 13 is removed (peeled off).

[0271] In this manner, a polarizing plate 10 including a polarizer 12 and a protective film 11 is obtained.

[0272] The resin base material 13 may not be removed and may be used as another functional layer. Specifically, the polarizing plate 10 may include the resin base material 13, the polarizer 12, and the protective film 11.

[0273] <Barrier film attachment process> In the barrier film attachment step, as shown in FIG. 4E, a barrier film 1 is attached to the surface of the protective film 11 opposite to the surface in contact with the polarizer 12 via an adhesive.

[0274] The adhesive is not particularly limited as long as it is an adhesive that is commonly used in the optical field. For example, an adhesive used for bonding the protective film 11 and the polarizer 12 is used, and preferably, an acrylic adhesive is used.

[0275] The thickness of the adhesive layer (cured adhesive) between the polarizing plate 10 and the barrier film 1 is, for example, 1 μm to 50 μm, preferably 5 μm to 40 μm, and more preferably 10 μm to 30 μm.

[0276] The thickness of the adhesive layer (cured adhesive) between the polarizing plate 10 and the barrier film 1 is, for example, 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and for example, 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less.

[0277] 5. Variations <Modifications of Barrier Film> In FIG. 1, in the barrier film 1, the barrier layer 4 is provided with an alternating laminate of a niobium oxide layer 41a, a silicon oxide layer 42a, a niobium oxide layer 41b, and a silicon oxide layer 42b, and an anti-fouling layer 43, arranged in that order in the thickness direction, but is not limited to this.

[0278] 9, the barrier layer 4 is made of a silicon oxide layer 42 (second layer) and an antifouling layer 43 arranged on one surface in the thickness direction of the silicon oxide layer 42. Although not shown, the barrier layer 4 may also be made of an alternating laminate made of a niobium oxide layer 41 (first layer) and a silicon oxide layer 42 (second layer), and an antifouling layer 43 arranged on one surface in the thickness direction of the alternating laminate.

[0279] That is, the barrier layer is not particularly limited as long as it includes at least one silicon oxide layer 42 and an antifouling layer 43 disposed on one side in the thickness direction of the silicon oxide layer 42. Specifically, the number and order of layers in the niobium oxide layer 41 and the silicon oxide layer 42 are not particularly limited.

[0280] <Manufacturing method of modified barrier film> A method for producing the barrier film 1 used in the barrier film-attached polarizing plate 100 shown in FIG. 9 will be described with reference to FIGS. 10A to 10E.

[0281] A manufacturing method of the barrier film 1 used in the barrier film-attached polarizing plate 100 shown in Fig. 9 includes, for example, a preparation step (Fig. 10A) of preparing a transparent resin film 21, a cured resin layer formation step (Fig. 10B) of forming a cured resin layer 22 on the transparent resin film 21, a primer layer formation step (Fig. 10C) of forming a primer layer 3 on the cured resin layer 22, a silicon oxide layer formation step (Fig. 10D) of forming a silicon oxide layer 42 on the primer layer 3, and an antifouling layer formation step (Fig. 10E) of forming an antifouling layer 43 on the silicon oxide layer 42. The primer layer formation step and the silicon oxide layer formation step are sequentially performed using an apparatus Z as shown in Fig. 5.

[0282] In the following description, descriptions similar to those of the manufacturing method of the barrier film 1 shown in FIG. 2 will be omitted.

[0283] <Silicon oxide layer forming process> Specifically, in the silicon oxide layer forming step, a silicon oxide layer 42 is formed on one surface of the primer layer 3 in the thickness direction by a sputtering method.

[0284] In the sputtering method, a sputtering film-forming apparatus such as the above-mentioned apparatus Z, which can perform a film-forming process by a roll-to-roll method, is used. When a roll-to-roll sputtering film-forming apparatus is used in the silicon oxide layer forming step, a transparent base film 2 having a primer layer 3 as a workpiece film W is run from a delivery roll 52 to a take-up roll 53, while a material for the silicon oxide layer (specifically, silicon) is formed on one surface in the thickness direction of the primer layer 3 to form a silicon oxide layer 42. The running speed of the workpiece film W (the transparent base film 2 having the primer layer 3) is, for example, 0.5 to 10.0 m / min. In the silicon oxide layer forming step, a magnet unit 75 of the second magnetron plasma unit 64 shown in FIG. 8 is used.

[0285] In the sputtering method in the silicon oxide layer forming process, a sputtering deposition apparatus having one deposition chamber R may be used, or a sputtering deposition apparatus having multiple deposition chambers R arranged in order along the travel path of the workpiece film W (transparent substrate film 2 having a primer layer 3) as shown in FIG. 5 may be used. When using an apparatus Z as shown in FIG. 5, deposition is required in only one deposition chamber (e.g., R2). When forming an alternating laminate consisting of a niobium oxide layer 41 (first layer) and a silicon oxide layer 42 (second layer), deposition is required in two deposition chambers (e.g., R1 and R2).

[0286] Specifically, in the sputtering method, a sputtering gas (inert gas) is introduced into the film formation chamber R under vacuum conditions, while a negative voltage is applied to the target arranged on the outer circumferential surface of the rotary target 74 in the film formation chamber R. This generates a glow discharge to ionize the gas atoms, and these gas ions collide with the target surface at high speed, ejecting the target material from the target surface, and the ejected target material is deposited in order in the thickness direction. Silicon is used as the target material.

[0287] The sputtering conditions are the same as those for the silicon oxide layer 42a (second layer) in the method for producing the barrier film 1 shown in FIG.

[0288] In this manner, the silicon oxide layer 42 is formed on one surface of the primer layer 3 in the thickness direction. EXAMPLES

[0289] The present invention will be described in more detail below with reference to examples, comparative examples and reference examples. The present invention is not limited to the examples, comparative examples and reference examples. The specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters and the like used in the following description can be replaced with the upper limit (numeric value defined as "less than or equal to" or "less than") or lower limit (numeric value defined as "more than or equal to" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters and the like described in the above "Form for carrying out the invention".

[0290] Example 1 <Preparation of protective film> Methyl methacrylate (MMA), 2-(hydroxymethyl)methyl acrylate (MHMA), toluene, and polystyrene were charged into a reaction vessel equipped with a stirrer, a temperature sensor, a cooling tube, and a nitrogen inlet tube, and a cyclization condensation reaction and degassing were carried out in an extruder at 250°C to obtain transparent lactone ring-containing acrylic resin pellets. The obtained pellets were put into a single-screw extruder, melt-mixed, and passed through a T-die to form a film. The obtained extruded film was simultaneously biaxially stretched twice in both the length and width directions at a stretching temperature of 160°C. The thickness of the obtained film was 40 μm. The resin composition ratio of the obtained film was confirmed by NMR, and it was 76% MMA, 19% lactone ring, and 5% styrene.

[0291] <Preparation of polarizing plate> A long amorphous isophthalic acid copolymerized polyethylene terephthalate film (water absorption rate: 0.75%, glass transition temperature: 75°C, thickness: 100μm) was prepared as a resin substrate. Next, one side of the resin substrate was corona treated. On this corona treated surface, an aqueous solution containing polyvinyl alcohol (polymerization degree: 4200, saponification degree: 99.2 mol%) and acetoacetyl modified polyvinyl alcohol (trade name: Gohsefimer Z200, polymerization degree: 1200, acetoacetyl modified degree: 4.6%, saponification degree: 99.0 mol% or more, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) in a ratio of 9:1 was applied and dried at 25°C to form a coating film (PVA film) of polyvinyl alcohol resin with a thickness of 11μm, and a substrate with a PVA film was obtained.

[0292] Thereafter, the substrate with the PVA film was uniaxially stretched at free end 2.0 times in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 120°C (air-assisted stretching). Next, the substrate with the PVA film was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by mass of boric acid with 100 parts by mass of water) at a liquid temperature of 30°C for 30 seconds (insolubilizing treatment). Next, the substrate was immersed in a dyeing bath at a liquid temperature of 30°C while adjusting the iodine concentration and immersion time so that the polarizing plate had a predetermined transmittance. Specifically, the substrate was immersed in an iodine aqueous solution obtained by mixing 0.2 parts by mass of iodine and 1.5 parts by mass of potassium iodide with 100 parts by mass of water for 60 seconds (dyeing treatment). Next, the substrate was immersed in a crosslinking bath (a boric acid aqueous solution obtained by blending 3 parts by mass of potassium iodide and 3 parts by mass of boric acid with respect to 100 parts by mass of water) with a liquid temperature of 30° C. for 30 seconds (crosslinking treatment). After that, the substrate with the PVA film was immersed in a boric acid aqueous solution (aqueous solution obtained by blending 4 parts by mass of boric acid and 5 parts by mass of potassium iodide with respect to 100 parts by mass of water) with a liquid temperature of 70° C., while being uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds so that the total stretch ratio was 5.5 times (underwater stretching). After that, the substrate with the PVA film was immersed in a cleaning bath (aqueous solution obtained by blending 4 parts by mass of potassium iodide with respect to 100 parts by mass of water) with a liquid temperature of 30° C. (cleaning treatment).

[0293] Next, the adhesive shown below was applied to the surface of the polyvinyl alcohol resin coating film (polarizer) of the PVA film-attached substrate so that the adhesive layer would have a thickness of 1.0 μm after curing, and the methacrylic resin film (thickness: 40 μm, moisture permeability: 100 g / m) prepared above was used as a protective film. 2 / 24h) was attached, and the methacrylic resin film side was heated to 50°C using an IR heater, and ultraviolet light was irradiated under the following conditions to cure the adhesive. Thereafter, the resin substrate was peeled off from the polarizer to obtain a polarizing plate (a polarizing plate comprising a polarizer and a protective film). The polarizer had a thickness of 5 μm and a single transmittance of 42.3%. The moisture content of the obtained polarizing plate was 1.0% by mass.

[0294] (Adhesive composition) An adhesive with a viscosity of 40 mPa·S before curing was prepared by mixing 40 parts by mass of N-hydroxyethylacrylamide (HEAA), 60 parts by mass of acryloylmorpholine (ACMO), and 3 parts by mass of the photoinitiator "IRGACURE819" (BASF).

[0295] (UV conditions) As an active energy ray, ultraviolet light (gallium-filled metal halide lamp, irradiation device: LightHAMMER10 manufactured by FusionUVSystems, Inc., bulb: V bulb, peak irradiance: 1600 mW / cm 2 , cumulative irradiation dose 1000mJ / cm 2 (Wavelength 380-440 nm) was used. The illuminance of the ultraviolet light was measured using a Sola-Check system manufactured by Solatell.

[0296] <Preparation of Barrier Film> A barrier film was prepared as follows.

[0297] [Preparation of transparent substrate film] 83 parts by mass of an acrylic monomer composition containing nanosilica particles (trade name: NC035HS, solid content concentration: 60% by mass, manufactured by Arakawa Chemical Industries Co., Ltd.), 17 parts by mass of an ultraviolet-curable multifunctional urethane acrylate (trade name: Beamset 580, solid content concentration: 70% by mass, manufactured by Arakawa Chemical Industries Co., Ltd.), 1.5 parts by mass of a photopolymerization initiator (trade name: OMNIRAD127D, manufactured by IGM Resins), 0.15 parts by mass of a leveling agent (trade name: LE303, solid content concentration: 40% by mass, manufactured by Kyoeisha Chemical Co., Ltd.), and butyl acetate were mixed to prepare a curable resin composition with a solid content concentration of 42% by mass. This composition was applied to one side of a 100 μm-thick triacetylcellulose film (trade name: Fujitac, manufactured by Fuji Film Co., Ltd.) so that the thickness after drying was 5 μm, and dried at 80 ° C. for 3 minutes. Thereafter, a high-pressure mercury lamp was used to apply an integrated light amount of 200 mJ / cm. 2 The coating layer was cured by irradiating it with ultraviolet light of 1000 nm to form a cured resin layer. In this manner, a transparent substrate film having a cured resin layer on the transparent resin film was obtained.

[0298] [Formation of primer layer] Next, a 4 nm thick ITO layer (primer layer) was formed on one side of the transparent substrate film in the thickness direction (one side of the cured resin layer in the thickness direction) by reactive sputtering. A roll-to-roll sputtering deposition apparatus Z (magnetron sputtering deposition apparatus Z) as shown in FIG. 5 was used to form the primer layer. The sputtering deposition apparatus Z has a deposition chamber in which the deposition process can be performed while running the work film (transparent substrate film) by the roll-to-roll method. The sputtering deposition apparatus Z used to form the primer layer also has a magnet unit of the first magnetron plasma unit shown in FIG. 7. Details of the magnet unit of the first magnetron plasma unit and the sputtering deposition conditions used to form the primer layer are shown below.

[0299] The magnet unit of the first magnetron plasma unit used first to fourth magnetic pole parts with an opposite side length L of 13 mm and a separation distance D (side length) between the opposite side and the fixed side of 13 mm. The second and third magnetic pole parts were N poles, and the first and fourth magnetic pole parts were S poles. The magnetization directions of the second and third magnetic pole parts were perpendicular to the width direction of the fixed member, and the magnetization directions of the first and fourth magnetic pole parts were parallel to the width direction of the fixed member. With this configuration, the sputtering angle (angle θ) can be set to approximately 42 degrees.

[0300] The ultimate vacuum level in the deposition chamber of the sputter deposition equipment is 1.0×10 -4After evacuating the chamber to 0.2 Pa, argon as a sputtering gas and oxygen as a reactive gas were introduced into the chamber, and the pressure in the chamber was set to 0.2 Pa. The argon gas and oxygen gas were introduced into the chamber so that the volume ratio between them was 100:10. As the target of the sputtering device, a sintered body of indium oxide and tin oxide was used, which contained indium oxide and tin oxide in a mass ratio of 90:10. As the power source for applying voltage to the target, an MFAC power source was used, with a discharge power of 4.3 kW and a film formation temperature (the temperature of the transparent substrate film on which the primer layer is formed) of -8°C.

[0301] In this manner, a primer layer was formed on one surface in the thickness direction of the transparent substrate film (one surface in the thickness direction of the cured resin layer).

[0302] [Barrier layer formation] Next, a reactive sputtering method was used to form an alternating laminate having a 16 nm thick niobium oxide layer (first layer), a 38 nm thick silicon oxide layer (second layer), a 30 nm thick niobium oxide layer (third layer), and a 98 nm thick silicon oxide layer (fourth layer) in sequence toward one side in the thickness direction on one side of the thickness direction of the primer layer. A roll-to-roll magnetron sputtering deposition apparatus Z as shown in FIG. 5 was used to form the alternating laminate. The apparatus is equipped with multiple deposition chambers that can perform a deposition process while running a work film (transparent substrate film with a primer layer) by a roll-to-roll method. The sputtering deposition apparatus used to form the alternating laminate is equipped with a magnet unit of the second magnetron plasma unit shown in FIG. 8. Details of the magnet unit of the second magnetron plasma unit and the sputtering deposition conditions used to form the alternating laminate are shown below.

[0303] The magnet unit of the second magnetron plasma unit used the first to fourth magnetic poles with a length L of the opposite side of 10 mm and a distance D (length of the side) between the opposite side and the fixed side of 20 mm. The second and third magnetic poles were N poles, and the first and fourth magnetic poles were S poles. The magnetization directions of the second and third magnetic poles were inclined in the thickness and width directions of the fixed member and crossed each other toward the center of the film-forming roll, and the magnetization directions of the first and fourth magnetic poles were parallel to the width direction of the fixed member. With this configuration, the sputtering angle (angle θ) can be set to about 30 degrees.

[0304] In the deposition of the first layer, the ultimate vacuum in the deposition chamber of the sputter deposition equipment was 1.0×10 -4 After evacuating the chamber to 0.5 Pa, argon as a sputtering gas and oxygen as a reactive gas were introduced into the chamber, and the pressure in the chamber was set to 0.5 Pa. The argon gas and oxygen gas were introduced into the chamber at a volume ratio of 100:5. Niobium was used as the target of the sputtering device. An MFAC power supply was used as the power supply for applying voltage to the target, with a discharge power of 13 kW and a film formation temperature (the temperature of the transparent substrate film having a primer layer on which the alternating laminate was formed) of -8°C.

[0305] In the deposition of the second layer, the ultimate vacuum in the deposition chamber of the sputter deposition equipment was 1.0×10 -4 After evacuating the chamber to 0.2 Pa, argon as a sputtering gas and oxygen as a reactive gas were introduced into the chamber, and the pressure in the chamber was set to 0.2 Pa. The argon gas and oxygen gas were introduced into the chamber at a volume ratio of 100:30. Silicon was used as the target of the sputtering device. An MFAC power supply was used as the power supply for applying voltage to the target, with a discharge power of 25 kW and a film formation temperature (the temperature of the transparent substrate film with a primer layer on which the alternating laminate was formed) of -8°C.

[0306] The third layer was formed under the same conditions as those for the first layer, except that the discharge power was 25 kW.

[0307] The fourth layer was formed under the same conditions as those for forming the second layer, except that the discharge power was 20 kW.

[0308] In this way, an alternating laminate was formed on one thickness-wise surface of the primer layer, having a niobium oxide layer (first layer), a silicon oxide layer (second layer), a niobium oxide layer (third layer), and a silicon oxide layer (fourth layer) in that order toward one side in the thickness direction.

[0309] Thereafter, an antifouling layer having a thickness of 8 nm was formed on one surface in the thickness direction of the alternate laminate (one surface in the thickness direction of the fourth layer) by a vacuum deposition method. As a material for the antifouling layer, an antifouling layer composition (product name: SHIN-ETSU SUBELYN KY1903-1, active ingredient: alkoxysilane compound containing a perfluoropolyether skeleton, manufactured by Shin-Etsu Chemical Co., Ltd.) that was dried and solidified was used as a deposition source, and the heating temperature of the deposition source was set to 260°C.

[0310] In this way, an antifouling layer was formed on one surface in the thickness direction of the silicon oxide layer. That is, a barrier layer was formed on one surface in the thickness direction of the primer layer. The barrier layer had a niobium oxide layer (first layer), a silicon oxide layer (second layer), a niobium oxide layer (third layer), a silicon oxide layer (fourth layer), and an antifouling layer in that order toward one side in the thickness direction.

[0311] In this manner, a barrier film was formed.

[0312] <Preparation of polarizing plate with barrier film> A cycloolefin film (refractive index characteristic: nx>ny>nz, in-plane phase difference: 116 nm) as a first retardation layer and a modified polyethylene film (refractive index characteristic: nz>nx>ny, in-plane phase difference: 35 nm) as a second retardation layer were sequentially attached to the polarizer surface of the polarizing plate. The ultraviolet-curing adhesive used for attaching the polarizer and the protective film was used for attachment. The first retardation layer was attached so that the slow axis of the first retardation layer was at an angle of 0° to the absorption axis of the polarizer, and the second retardation layer was attached so that the slow axis of the second retardation layer was at an angle of 90° to the absorption axis of the polarizer. Furthermore, the barrier film was attached to the surface of the protective film (methacrylic resin film) of the polarizing plate via an acrylic adhesive (thickness: 20 μm) to obtain a polarizing plate with a barrier film. The transparent substrate film of the barrier film was attached to the surface of the protective film of the polarizing plate via the acrylic adhesive so that it was in contact with the surface of the protective film of the polarizing plate.

[0313] Example 2 The barrier film-attached polarizing plate of Example 2 was produced in the same manner as the barrier film-attached polarizing plate of Example 1, except that an alternating laminate having a niobium oxide layer (first layer) having a thickness of 5 nm and a silicon oxide layer (second layer) having a thickness of 135 nm, arranged in that order toward one side in the thickness direction, was formed on one surface of the primer layer in the barrier film. That is, in Example 2, the third and fourth layers were not formed in the barrier film.

[0314] Example 3 Except for forming only a 135 nm-thick silicon oxide layer (second layer) on one surface of the barrier film in the thickness direction of the primer layer, the barrier film-attached polarizing plate of Example 3 was produced in the same manner as the barrier film-attached polarizing plate of Example 1. That is, in Example 3, the first layer, the third layer, and the fourth layer were not formed on the barrier film.

[0315] Comparative Example 1 The barrier film-attached polarizing plate of Comparative Example 1 was produced in the same manner as the barrier film-attached polarizing plate of Example 3, except that the sputtering deposition apparatus used in the primer layer formation process (specifically, the sputtering deposition apparatus equipped with the magnet unit of the first magnetron plasma unit shown in Figure 7) was used to form the silicon oxide layer (second layer) in the barrier film.

[0316] Comparative Example 2 The barrier film-attached polarizing plate of Comparative Example 3 was produced in the same manner as the barrier film-attached polarizing plate of Example 1, except that the sputtering deposition apparatus used in the primer layer formation process (specifically, the sputtering deposition apparatus equipped with the magnet unit of the first magnetron plasma unit shown in Figure 7) was used to form the niobium oxide layer (first layer), silicon oxide layer (second layer), niobium oxide layer (third layer), and silicon oxide layer (fourth layer) in the barrier film.

[0317] Reference example 1 A polarizing plate with a barrier film of Reference Example 1 was produced in the same manner as the polarizing plate with a barrier film of Comparative Example 3, except for the following.

[0318] In the polarizing plate, a polyvinyl alcohol film with an average degree of polymerization of 2700 and a thickness of 75 μm was used as a polarizer, which was stretched six times while being dyed with iodine. Next, a transparent film with a thickness of 30 μm made of a modified acrylic polymer having a lactone ring structure was attached to the polarizer. For attachment, an adhesive made of an aqueous solution containing a polyvinyl alcohol resin (average degree of polymerization 1200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) containing an acetoacetyl group and methylolmelamine in a weight ratio of 3:1 was used, and the films were attached using a roll laminator, and then heated and dried in an oven. In this way, a polarizing plate was obtained.

[0319] Reference example 2 A polarizing plate with a barrier film of Reference Example 2 was produced in the same manner as the polarizing plate with a barrier film of Example 1, except for the following.

[0320] In the barrier film, a cured resin coating layer containing silica particles was formed as a barrier layer on one surface in the thickness direction of the transparent substrate film (one surface in the thickness direction of the cured resin layer). Specifically, the following cured resin coating liquid containing silica particles was applied to one surface in the thickness direction of the transparent substrate film (one surface in the thickness direction of the cured resin layer) with a wire bar. The applied coating liquid was heated at 80°C for 1 minute and dried to form a coating film. The dried coating film was irradiated with a high-pressure mercury lamp with an integrated light quantity of 300 mJ / cm. 2 The coating was cured by irradiating it with ultraviolet light of 100 nm, thereby forming a cured resin coating layer containing silica particles having a thickness of 100 nm.

[0321] [Preparation of curable resin coating solution containing silica particles] 100 parts by mass of a polyfunctional acrylate having pentaerythritol triacrylate as a main component (trade name: Viscoat #300, solid content: 100% by mass, manufactured by Osaka Organic Chemical Industry Co., Ltd.), 100 parts by mass of hollow nanosilica particles (trade name: Sururia 5320, solid content: 20% by mass, mass average particle diameter: 75 nm, manufactured by JGC Catalysts and Chemicals Co., Ltd.), 30 parts by mass of solid nanosilica particles (trade name: MEK-2140Z-AC, solid content: 30% by mass, mass average particle diameter: 10 nm, manufactured by Nissan Chemical Industries, Ltd.), 12 parts by mass of a fluorine-containing additive (trade name: KY-1203, solid content: 20% by mass, manufactured by Shin-Etsu Chemical Co., Ltd.), and 3 parts by mass of a photopolymerization initiator (trade name: OMNIRAD907, solid content: 100% by mass, manufactured by BASF) were mixed. To the mixture was added a mixed solvent of TBA (tertiary butyl alcohol), MIBK (methyl isobutyl ketone), and PMA (propylene glycol monomethyl ether acetate) in a mass ratio of 60:25:15 as a dilution solvent, until the total solid content was 4 mass%, and the mixture was stirred to prepare a cured resin coating solution containing silica particles.

[0322] <Evaluation> [density] In each of the Examples, Comparative Examples, and Reference Example 1, the density of the silicon oxide layer closest to the antifouling layer in the thickness direction was measured by Rutherford backscattering (RBS) spectroscopy. The results are shown in Table 1. The density was calculated using the film thickness determined by the method described below.

[0323] In each Example, Comparative Example, and Reference Example 1, the thickness of the silicon oxide layer closest to the antifouling layer in the thickness direction was measured by observation with a field emission transmission electron microscope (FE-TEM). Specifically, first, a cross-sectional observation sample of the barrier film in each Example, Comparative Example, and Reference Example 1 was prepared by FIB microsampling. In the FIB microsampling method, an FIB device (product name: FB2200, manufactured by Hitachi) was used, and the acceleration voltage was set to 10 kV. Next, the cross section of the barrier film in the cross-sectional observation sample was observed by FE-TEM, and the thickness of the silicon oxide layer closest to the antifouling layer was measured in the observed image. In addition, in the observation, an FE-TEM device (product name: JEM-2800, manufactured by JEOL) was used, and the acceleration voltage was set to 200 kV.

[0324] [Moisture permeability] The polarizing plate with a barrier film in each Example, Comparative Example, and Reference Example was cut into a circle with a diameter of 15 cm to prepare a measurement sample. After leaving the measurement sample for 24 hours under conditions of a temperature of 40°C and a humidity of 92% RH, the moisture permeability was measured under test conditions of a temperature of 40°C and a humidity of 90% RH using a water vapor transmission rate measuring device (product name: Delta Palm, manufactured by Techno-I Co., Ltd.). The results are shown in Table 1.

[0325] [Chromaticity] The barrier film-attached polarizing plate (100 mm x 50 mm) of each Example, Comparative Example, and Reference Example was placed in a thermo-hygrostat at a temperature of 65°C and a humidity of 90% RH. The chromaticity b of the transmitted light of each barrier film-attached polarizing plate before (0 hours), after 240 hours and 500 hours of heating and humidifying conditions was * The chromaticity of the transmitted light measured at each time was measured using a spectrophotometer (product name: DOT-3, manufactured by Murakami Color Research Laboratory). *and the chromaticity of the transmitted light measured before the heating and humidifying conditions were applied b * The difference from the initial value is calculated using the following formula, and the change in chromaticity of the transmitted light Δb * The results are shown in Table 1. Change in chromaticity of transmitted light Δb * = (chromaticity of transmitted light before heating and humidification b * (Initial value))-(chromaticity of transmitted light measured at each time b * )

[0326] [Reflectance] The reflectance of the barrier film in each of the Examples, Comparative Examples, and Reference Examples was measured using an ultraviolet-visible-infrared spectrophotometer (product name: UH-4150, manufactured by Hitachi High-Tech Science Corporation). A black acrylic plate was attached to the transparent substrate film side of the barrier film using an adhesive to prepare a measurement sample. The measurement was performed at wavelengths of 380 nm to 780 nm. The results are shown in Table 1.

[0327] [Table 1] [Explanation of symbols]

[0328] 1. Barrier film 2. Transparent substrate film 3 Primer layer 4. Barrier Layer 21 Transparent resin film 22 Cured resin layer 41 Niobium oxide layer 42 Silicon oxide layer

Claims

1. A transparent substrate film including a transparent resin film; A barrier layer disposed on one side of the transparent substrate film in a thickness direction; Equipped with the barrier layer includes at least one silicon oxide layer and an antifouling layer disposed on one side of the silicon oxide layer in a thickness direction; The density of the silicon oxide layer closest to the antifouling layer in the thickness direction is 2.35 g / cm 3 That's it for the barrier film.

2. The barrier film according to claim 1 , wherein the transparent substrate film further comprises a cured resin layer disposed on one side in a thickness direction of the transparent resin film.

3. The barrier film further comprises a primer layer, The primer layer is a metal oxide layer, The barrier film according to claim 1 , wherein the primer layer is disposed on one side of the transparent substrate film in a thickness direction and on the other side of the barrier layer in the thickness direction.

4. 2. The barrier film according to claim 1, wherein the barrier layer comprises an alternating laminate including at least one niobium oxide layer and at least one silicon oxide layer, and the antifouling layer is disposed on one surface in a thickness direction of the alternating laminate.

5. The barrier film according to claim 1 , wherein the barrier layer comprises a silicon oxide layer and the antifouling layer disposed on one surface of the silicon oxide layer in a thickness direction.

6. A barrier film according to any one of claims 1 to 5, a polarizing plate disposed on the other side of the barrier film in the thickness direction; A polarizing plate with a barrier film.

7. The polarizing plate includes a protective film and a polarizer, The barrier film-attached polarizing plate according to claim 6 , wherein the polarizer is a coating film of a polyvinyl alcohol resin.

8. Change in chromaticity of transmitted light Δb under heating and humidifying conditions at 60°C and 90% RH for 240 hours * The barrier film-attached polarizing plate according to claim 6 , wherein the refractive index is 0.5 or less.

Citation Information

Patent Citations

  • Polarizing plate with Anti-reflection layer and method for producing same

    WO2019163461A1

Cited By

  • Optical laminate, article, and method for manufacturing optical laminate

    WO2026168317A1